Resist underlayer film-forming composition, resist underlayer film, method for manufacturing resist underlayer film, method for forming pattern, and method for manufacturing semiconductor device
By using the resist underlayer film composition of novolac resin and organic solvent, the problem of insufficient adhesion between the resist composition and the substrate in the photon nanoimprinting technology is solved, and a resist underlayer film with high processing resistance and good gas penetration is achieved.
Patent Information
- Application Number
- CN202411427818.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-16
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-18
AI Technical Summary
In the photonanoimprinting technology, the adhesion between the resist composition and the substrate is insufficient, resulting in the occurrence of pattern peeling defects in the demolding step, and the prior art fails to effectively improve gas penetration.
The composition for forming a resist lower film containing novolac resin and an organic solvent is used. The composition inhibits the accumulation and cross-linking reaction of aromatic rings through a specific repeating unit structure and substituent design, and improves the breathability and processing resistance of the film.
High processing resistance, excellent landfill and flatness of the resist lower layer film, and low film density and good gas penetration are achieved, reducing the occurrence of pattern peeling defects.
Smart Images

Figure CN119846902A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resist underlayer film forming composition, a resist underlayer film, a method for manufacturing the resist underlayer film, a pattern forming method, and a method for manufacturing a semiconductor device. In particular, the present invention relates to a resist underlayer film forming composition for nanoimprinting that can be used in fine patterning by photo-nanoimprinting in a semiconductor device manufacturing process. Background Art
[0002] In the manufacture of semiconductor devices, MEMS, etc. that require miniaturization, optical nanoimprinting technology that can form microstructures of the order of several nanometers on a substrate has attracted attention. In general optical nanoimprinting technology, first, a liquid resist composition is dripped into the pattern forming area on the substrate using an inkjet method, and the droplets of the resist composition are spread on the substrate (pre-smearing). Next, the resist composition is formed using a mold (mold) that is transparent to the irradiated light and has been patterned. At this time, the droplets of the resist composition will be spread over the entire range of the gap between the substrate and the mold due to the capillary phenomenon (smearing). The resist composition will also fill (fill) the inside of the concave portion on the mold due to the capillary phenomenon. The time until the smearing and filling are completed is the filling time. After the filling of the resist composition is completed, light is irradiated to harden the resist composition, and then the two are separated. By implementing these steps, a pattern of a resist having a predetermined shape will be formed on the substrate.
[0003] In the demolding step of the photo-nanoimprinting technology, the adhesion between the resist composition and the substrate is important. If the adhesion between the resist composition and the substrate is low, when the mold is separated in the demolding step, a part of the photocured material obtained by hardening the resist composition will be peeled off while attached to the mold, and there will be a situation where pattern peeling defects occur. In this context, as for the technology of improving the adhesion between the resist composition and the substrate, it has been proposed to form a bonding layer between the resist composition and the substrate as a layer for bonding the resist composition to the substrate (Patent Document 1).
[0004] In addition, Patent Document 2 discloses a reverse process in nanoimprinting. Since Spin On Carbon (SOC) is used as the processed layer, properties such as processing resistance, filling and flatness become necessary. In addition, in the nanoimprinting process on SOC, a close-contact layer material for nanoimprinting is generally coated on the SOC and imprinted thereon. In addition, when the mold is pressed against the curable composition (resist), poor shaping and the like may occur due to the generated bubbles, so the generated bubbles must be defoamed. In Patent Document 3, although the oxygen permeability on the mold side is improved, further improvement in defoaming is expected with the miniaturization. Considering this background, it has been proposed to defoam the gas from the lower film side and seek the development of a lower film with high air permeability (Non-Patent Document 1).
[0005] As for the permeability of gas, if it is a hydrophobic gas, it will be in a hydrophobic film, and if it is a highly hydrophilic gas, it will be in a hydrophilic film, and there will be a tendency for the permeability to increase. As for the gas environment in the step of pressing the mold tightly, relatively hydrophobic gases such as He, H2, N2, and air are selected, so patent documents 4 and 5 propose highly hydrophobic films with high water contact angles as the lower film material. However, these documents do not discuss the actual gas permeability. In fact, there is also the possibility of selecting highly hydrophilic gases such as CO2. On the other hand, as for air permeability, it is known that in addition to hydrophilicity and hydrophobicity, it will also be greatly affected by film density and admixtures.
[0006] Prior art literature
[0007] Patent Literature
[0008] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-202982
[0009] [Patent Document 2] Japanese Patent Publication No. 2006-524919
[0010] [Patent Document 3] Japanese Patent No. 6703253
[0011] [Patent Document 4] International Publication No. 2021-125036
[0012] [Patent Document 5] International Publication No. 2023-145923
[0013] Non-patent literature
[0014] [Non-patent document 1] Proc. SPIE 10958, Novel Patterning Technologies for Semiconductors, MEMS / NEMS, and MOEMS 2019, 109580H Summary of the invention
[0015] [Problems to be solved by the invention]
[0016] The present invention is made in view of the above situation, and its purpose is to provide a composition for forming a resist underlayer film that can form a resist underlayer film that exhibits excellent processing resistance and excellent gas permeability, a resist underlayer film that is a cured product of a coating film composed of the composition, a method for manufacturing a resist underlayer film using the composition, a pattern forming method, and a method for manufacturing a semiconductor device.
[0017] [Methods to solve the problem]
[0018] In order to solve the above-mentioned problems, the present invention provides a resist underlayer film-forming composition, characterized in that it comprises:
[0019] (A) a novolac resin having a repeating unit structure represented by the following general formula (I) and / or (II), and
[0020] (B) an organic solvent;
[0021] [Chemistry 1]
[0022]
[0023] In the general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted aryl groups having 6 to 30 carbon atoms bonded to each other via linear, branched or cyclic hydrocarbon groups, ether groups or carbonyl groups. Ar1 may be one or a combination of multiple groups in the same resin, and Ar2 may be one or a combination of multiple groups in the same resin. R1 in the same resin is A combination of at least two or more of them is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; n1 is an integer greater than 1, and n2, n3 and n4 are integers greater than 0.
[0024] The above-mentioned (A) component is a phenolic varnish resin, so the main skeleton contains an aromatic ring, and the mechanical strength (also known as processing resistance) for withstanding processing is excellent. Then, by setting R1 to a combination of at least two or more, there will be at least two repeating units with different OR1 in the same resin, and / or there will be repeating units containing more than two OR1 groups. The steric hindrance of the substituent introduced by the spacer ether structure can suppress the close stacking and dense cross-linking reaction between the aromatic rings, and can suppress the high density of the film obtained by the hardening of the composition. By suppressing high density, the film obtained by the hardening of the composition can exert excellent air permeability. By appropriately selecting the main skeleton structure and the substituent structure, the opposite performance of processing resistance and air permeability can be taken into account. In addition, by setting R1 to a combination of at least two or more, the crystallinity of the resin can be suppressed, and thermal fluidity can be given while suppressing the high density of the film. Therefore, the composition for forming an anti-etching underlayer film of the present invention can provide an anti-etching underlayer film that is expected to have excellent filling and flatness after calcination, good film hardness and mechanical strength that can withstand processing (good processing resistance); and low film density and good gas permeability.
[0025] In the above formulae (I) and (II), at least one of R1 is a structure R selected from the group consisting of groups represented by the following formula (III-1): 1-1 More ideal.
[0026] [Chemistry 2]
[0027]
[0028] In formula (III-1), * represents a bonding site with an oxygen atom.
[0029] In the above general formulae (I) and (II), if at least one of R1 is a structure R selected from the group consisting of the groups represented by the above general formula (III-1) 1-1 , there are many with a ring structure, which is not easy to damage the processing resistance. On the other hand, the ring structure itself has a low density and a large steric hindrance, so the effect of preventing the aromatic rings from being closely adjacent to each other is large, and a film with a low film density can be provided. That is, by using this preferred aspect of the resist underlayer film-forming composition, a resist underlayer film with excellent processing resistance and better air permeability can be provided.
[0030] Then, in the above formulae (I) and (II), R1 is a structure R selected from the group consisting of the groups shown in the following formula (III-1): 1-1 and a structure R selected from the group consisting of groups represented by the following formula (III-2): 1-2 Combination of structure R 1-1The ratio is set to a, and the structure R 1-2 When the ratio of is set to b, it is ideal that the ratios a and b satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100.
[0031] [Chemistry 3]
[0032]
[0033] In the formulae (III-1) and (III-2), * represents a bonding site to an oxygen atom.
[0034] In the above formulae (I) and (II), if R1 is a structure R selected from the group consisting of the groups shown in (III-1) above 1-1 and a structure R selected from the group consisting of the groups shown in (III-2) above 1-2 If the structure R 1-1 There are many with a ring structure, which is not easy to damage and processing resistance. On the other hand, the ring structure itself has a low density and a large steric hindrance, so it is effective in preventing the aromatic rings from being closely adjacent to each other, and a low film density film can be achieved. 1-2 It acts as a thermosetting group, so when the hardening property of the resin is insufficient when it is alone, the hardening property of the resin can be improved. In addition, by blocking the hydroxyl group, the hydrophobicity can be improved, the affinity with hydrophobic gases such as He and N2 can be improved, and the air permeability can be improved. Then, by including two or more different substituents, excellent solubility can be expected, and thermal fluidity is also excellent. Therefore, it can be expected that the processing tolerance is good during baking, and it has excellent landfill and flatness, and the film density is low, and the resist lower layer film with good air permeability can be shown.
[0035] In the above general formula (II), Ar2 is preferably a benzene ring.
[0036] In the above formula (II), when Ar2 is a benzene ring, various raw materials having different substituents can be obtained, so that the physical properties can be adjusted in accordance with the required performance.
[0037] In the above general formulae (I) and (II), Ar1 is preferably selected from the group consisting of structures shown in the following formula (Ar-1).
[0038] [Chemistry 4]
[0039]
[0040] In the above general formulas (I) and (II), if Ar1 is a benzene ring or a naphthalene ring, the monomer itself is rich in variety, and the substituent can be selected to adjust various physical properties by matching the required performance. In addition, the other structures shown in the above formula (Ar-1) all have two benzene rings in one molecule and they are bonded by straight chain, cyclic alkyl, ether group, or condensed, so that a structure that can inhibit the accumulation of aromatic rings can be formed, which can inhibit the film from becoming high density after baking. Therefore, it will show good air permeability and good flatness of the resist lower layer film.
[0041] In the above general formula (II), n3+n4 is preferably an integer of 2 or more.
[0042] When n3+n4 is an integer greater than or equal to 2 in the general formula (II), the number of substituents increases, so that the effects of suppressing stacking and suppressing crystallinity can be enhanced.
[0043] The novolac resin (A) preferably has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 8,000 as determined by gel permeation chromatography.
[0044] If the weight average molecular weight Mw of the above-mentioned (A) phenolic varnish resin is 2000-8000, the low molecular weight components that will become the cause of sublimation during baking will be reduced, so poor film formation will be less likely to occur, and the composition for forming the lower layer film can also be prevented from having poor filling properties due to reduced thermal fluidity caused by excessively large molecular weight.
[0045] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and
[0046] After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.
[0047] Ideally, 100.5<{(FT-2) / (FT-1)}×100.
[0048] If it becomes 100.5<{(FT-2) / (FT-1)}×100, the reworked membrane is swollen compared to the membrane just after calcination. It is believed that a porous membrane with a large number of fine pores such as OK73 diluent can penetrate is formed just after calcination, indicating that a membrane with low membrane density is formed instead of a dense membrane. Therefore, the membrane obtained by the composition of this state can be expected to be a membrane with excellent air permeability.
[0049] It is preferred that (C) a surfactant is further contained.
[0050] The surfactant (C) can suppress film formation defects such as streaking on the film surface and disturbance of in-plane uniformity.
[0051] further comprising (D) a cross-linking agent,
[0052] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and
[0053] After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.
[0054] Ideally, 100<{(FT-2) / (FT-1)}×100<101.
[0055] The crosslinking agent (D) can accelerate curing when the curing of the resin alone is insufficient, and in addition to increasing the hardness of the film and enhancing the processing resistance, it can also suppress swelling of the film after reworking, thereby adjusting the porosity of the film.
[0056] It further contains (E) a thermally decomposable resin,
[0057] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and
[0058] After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.
[0059] It is also ideal that 101<{(FT-2) / (FT-1)}×100.
[0060] By including the (E) pyrolyzable resin, the pyrolyzable resin decomposes during baking and sublimates from the film, thereby further forming pores in the film. As a result, the swelling of the film after reworking increases, and the degree of porosity of the film can be adjusted.
[0061] further comprising (D) a crosslinking agent and (E) a thermally decomposable resin,
[0062] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and
[0063] After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.
[0064] It is also ideal that 100<{(FT-2) / (FT-1)}×100.
[0065] (D) The cross-linking agent and (E) the thermally decomposable resin have opposite effects as the density adjuster of the film, so when both are contained at the same time, it is sufficient to confirm the hardening of the film. Therefore, when comparing the difference in film thickness before and after reworking, it is sufficient to have (FT-2)>(FT-1).
[0066] Then, (F) an acid generator may be further contained.
[0067] By including (F) an acid generator, the curability of the resin and the decomposability of the thermally decomposable resin may be improved.
[0068] The resist underlayer film forming composition of the present invention can also be used for nanoimprinting.
[0069] The use of the resist underlayer film formed by the composition of the present invention is not particularly limited. For example, the resist underlayer film-forming composition of the present invention can also be used for nanoimprinting. The resist underlayer film formed by the resist underlayer film-forming composition of the present invention has good processing resistance, excellent filling and flatness, and low film density and can show good air permeability. Therefore, by using the composition of the present invention, a resist underlayer film that is very useful for nanoimprinting can be realized.
[0070] Furthermore, the present invention provides a resist underlayer film which is a cured product of a coating film composed of the resist underlayer film forming composition of the present invention.
[0071] The resist underlayer film formed using the resist underlayer film-forming composition of the present invention has good processing resistance, excellent filling property and flatness, and has a low film density and can exhibit good air permeability.
[0072] Furthermore, the present invention provides a method for manufacturing a resist underlayer film, characterized in that it comprises the following steps:
[0073] The resist underlayer film forming composition of the present invention is applied on a semiconductor substrate to obtain a coating film,
[0074] The coated film is fired to obtain a resist underlayer film.
[0075] If this is the method for manufacturing the resist underlayer film of the present invention, since the resist underlayer film-forming composition of the present invention is used, a resist underlayer film having good processing resistance, excellent filling property and flatness, low film density, and good air permeability can be achieved.
[0076] Furthermore, the present invention provides a pattern forming method, characterized in that it comprises the following steps:
[0077] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0078] forming a hardening composition film on the resist underlayer film,
[0079] The curable composition film is brought into contact with a mold,
[0080] The curable composition film is irradiated with light or electron beam to form a cured film.
[0081] The cured film is separated from the mold.
[0082] By using the pattern forming method of the imprint method of the present invention, it is possible to utilize a resist underlayer film that has good processing resistance, excellent filling property and flatness, low film density, and good air permeability. Therefore, by using the pattern forming method of the imprint method of the present invention, it is possible to quickly remove bubbles generated when the mold is pressed against the curable composition film, and to form a fine pattern.
[0083] The step of forming a curable composition film on the resist underlayer film may include: forming a bonding layer and / or a polysilicon oxide layer containing 99 mass % or less of Si on the resist underlayer film by coating or evaporation, and forming the curable composition film thereon.
[0084] By forming the adhesion layer, pattern peeling can be sufficiently suppressed in the step of separating the mold. In addition, by forming a polysilicon layer containing 99 mass % or less of Si, the optical properties of the film can be adjusted, and reflection control can be performed.
[0085] Furthermore, the present invention provides a method for manufacturing a semiconductor device, characterized by comprising the following steps:
[0086] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0087] forming a resist film on the resist underlayer film,
[0088] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0089] Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film,
[0090] The semiconductor substrate is processed using the patterned underlayer film as a mask.
[0091] Furthermore, the present invention provides a method for manufacturing a semiconductor device, characterized by comprising the following steps:
[0092] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0093] forming a hard mask on the resist underlayer film,
[0094] Then, a resist film is formed on the hard mask film.
[0095] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0096] The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask,
[0097] Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film,
[0098] The semiconductor substrate is processed using the patterned resist underlayer film as a mask.
[0099] The resist underlayer film-forming composition of the present invention can provide a resist underlayer film having good processing resistance, excellent filling property and flatness, low film density, and good air permeability, so as mentioned above, it is also useful in a method for manufacturing a semiconductor device using a pattern forming method other than the nanoimprint method, such as a multilayer resist method. That is, by the method for manufacturing a semiconductor device of the present invention, a fine pattern can be formed on a semiconductor substrate.
[0100] [Effects of the Invention]
[0101] As described above, the resist film-forming composition of the present invention comprises: (A) a novolac resin having a repeating unit structure represented by the above general formula (I) and / or (II), and (B) a composition of an organic solvent. Since the novolac resin (A) contains an aromatic ring, it has sufficient mechanical strength to withstand processing, and since it can inhibit the close stacking and dense cross-linking reaction between the aromatic rings, it can suppress the film from becoming high-density. Therefore, the resist underlayer film-forming composition of the present invention can provide a resist underlayer film having good processing resistance, excellent embedding property and flatness, low film density, and good air permeability.
[0102] Furthermore, the resist underlayer film of the present invention can exhibit good processing resistance, excellent filling properties and planarity, and can exhibit good gas permeability with a low film density.
[0103] Furthermore, by the method for forming a resist underlayer film of the present invention, a resist underlayer film can be manufactured which exhibits good processing resistance, excellent filling property and flatness, low film density, and good air permeability.
[0104] Furthermore, according to the pattern forming method of the present invention, bubbles generated when the mold is pressed against the curable composition film can be quickly removed, thereby forming a fine pattern.
[0105] Furthermore, by using the method for manufacturing a semiconductor device of the present invention, a semiconductor device having a fine pattern formed on a semiconductor substrate can be manufactured. DETAILED DESCRIPTION
[0106] As described above, in order to form a resist underlayer film capable of transferring a resist pattern onto a substrate to be processed with higher precision in fine patterning, the development of an underlayer film having excellent embedding properties and processing resistance and high air permeability is sought.
[0107] The inventors of the present application have repeatedly conducted intensive research on the above-mentioned topics, and as a result, they have focused on the characteristics of polymers containing aromatic rings that have sufficient mechanical strength but will become dense films due to accumulation, and have considered the introduction of structures that will hinder accumulation, and have repeatedly conducted intensive research. As mentioned above, the optical nanoimprinting technology that can form a microstructure of the order of several nanometers on a substrate is a target of attention, but there will be problems caused by bubbles generated when the mold is pressed tightly, and defects have been generated. So far, improvements have been made on the gas permeability of the mold side. On the other hand, improvements on the mold side alone are currently insufficient, and defoaming is also considered from the lower film (resist lower film) side, but there is no progress in material development, and there are still few options. When used as a lower film, a material that also has processing resistance and flattening characteristics is more ideal. The inventors of the present application focused on phenolic varnish resins with excellent processing resistance, and believed that by etherifying at least one hydroxyl group in the phenolic varnish resin, the accumulation of aromatic rings can be suppressed, a film with low film density can be formed, and a film with high air permeability can be formed. Furthermore, it is considered that by introducing a plurality of ether substituents, the stacking suppression effect can be enhanced and fluidity can be imparted, thereby providing a resist underlayer film-forming composition having excellent filling properties and planarization characteristics.
[0108] The inventors of the present application have further repeated and in-depth research and found that if the composition contains: (A) a phenolic varnish resin having a repeating unit structure represented by the above-mentioned general formula (I) and / or (II), and (B) an organic solvent, it will be expected to have mechanical strength that can withstand processing, excellent filling properties and flatness, and a low film density, so it is excellent in air permeability. The present invention has been completed.
[0109] That is, the present invention is a composition for forming a resist underlayer film, characterized in that it comprises: (A) a novolac resin having a repeating unit structure represented by the following general formula (I) and / or (II), and
[0110] (B) Organic solvent.
[0111] [Chemistry 5]
[0112]
[0113] In the general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted aryl groups having 6 to 30 carbon atoms bonded to each other via linear, branched or cyclic hydrocarbon groups, ether groups or carbonyl groups. Ar1 may be one or a combination of multiple groups in the same resin, and Ar2 may be one or a combination of multiple groups in the same resin. R1 in the same resin is A combination of at least two or more of them is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; n1 is an integer greater than 1, and n2, n3 and n4 are integers greater than 0.
[0114] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.
[0115] <Resist Underlayer Film Forming Composition>
[0116] The resist underlayer film-forming composition of the present invention is characterized by comprising: (A) a novolac resin having a repeating unit structure represented by the following general formula (I) and / or (II), and (B) an organic solvent.
[0117] [Chemistry 6]
[0118]
[0119] In the general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted aryl groups having 6 to 30 carbon atoms bonded to each other via linear, branched or cyclic hydrocarbon groups, ether groups or carbonyl groups. Ar1 may be one or a combination of multiple groups in the same resin, and Ar2 may be one or a combination of multiple groups in the same resin. R1 in the same resin is A combination of at least two or more of them is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; n1 is an integer greater than 1, and n2, n3 and n4 are integers greater than 0.
[0120] In the composition for forming the resist lower film of this invention, the above-mentioned (A) component is a phenolic varnish resin, so the main skeleton contains an aromatic ring, and the mechanical strength (also known as processing resistance) for withstanding processing is excellent. Then, by setting R1 to a combination of at least two or more, at least two repeating units with different OR1 and / or repeating units containing more than two OR1 groups will exist in the same resin. The steric hindrance of the substituent introduced by the spacer ether structure can inhibit the close stacking and dense cross-linking reaction between the aromatic rings, and can inhibit the high density of the film obtained by the hardening of the composition. By inhibiting high density, the film obtained by the hardening of the composition can exert excellent air permeability. By appropriately selecting the main skeleton structure and the substituent structure, the opposite performances of processing resistance and air permeability can be taken into account. In addition, by setting R1 to a combination of at least two or more, the crystallinity of the resin can be suppressed, and thermal fluidity can be given while suppressing the high density of the film. Therefore, the resist underlayer film-forming composition of the present invention can provide a resist underlayer film that is expected to have good processing resistance, excellent filling properties and flatness, low film density, and good air permeability.
[0121] By means of the resist underlayer film forming composition of the present invention, a resist underlayer film that can be used in various pattern forming methods can be formed. For example, the resist underlayer film formed by the resist underlayer film forming composition of the present invention can also be used as a resist underlayer film in a pattern forming method using a multilayer resist process, can also be used as a resist underlayer film in a pattern forming method using an imprinting method, and can also be used in pattern forming methods other than these. In particular, as previously described, the resist underlayer film formed by the resist underlayer film forming composition of the present invention has good processing resistance, excellent filling and flatness, and has a low film density and can exhibit good air permeability. Therefore, by means of the resist underlayer film forming composition of the present invention, a resist underlayer film that is very useful for nanoimprinting can be realized.
[0122] Hereinafter, each component of the resist underlayer film forming composition of the present invention will be described in more detail.
[0123] <(A) Novolac Resin>
[0124] In the above general formulas (I) and (II), R1 is a combination of at least two or more in the same resin, which are hydrogen atoms, substituted or unsubstituted straight-chain, branched or cyclic alkyl groups with 1 to 20 carbon atoms, substituted or unsubstituted straight-chain, branched or cyclic alkenyl groups with 2 to 20 carbon atoms, or substituted or unsubstituted straight-chain, branched or cyclic alkynyl groups with 2 to 20 carbon atoms. Two or more can be used in combination according to the desired characteristics. For example, from the perspective of suppressing the accumulation of aromatic rings and dense cross-linking reactions, straight-chain alkyl groups such as n-hexyl and n-octyl, branched alkyl groups such as neopentyl, cyclic alkyl groups such as methylcyclohexyl and methyladamantyl, and cyclic ether groups such as methyltetrahydrofuran are more ideal. From the perspective of maintaining processing resistance, cyclic alkyl groups and ether groups are more ideal. From the perspective of thermosetting properties, unsaturated bonds are more ideal.
[0125] In the above general formulae (I) and (II), specific structures other than the hydrogen atom of R1 include the following structures, but are not limited to these structures: * is a bonding site with oxygen.
[0126] [Chemistry 7]
[0127]
[0128] In the above formulae (I) and (II), at least one of R1 is a structure R selected from the group consisting of groups represented by the following formula (III-1): 1-1 More ideal.
[0129] [Chemistry 8]
[0130]
[0131] In formula (III-1), * represents a bonding site with an oxygen atom.
[0132] In the above general formulae (I) and (II), if at least one of R1 is a structure R selected from the group consisting of the groups represented by the above general formula (III-1) 1-1 , there are many with a ring structure, which is not easy to damage the processing resistance. On the other hand, the ring structure itself has a low density and a large steric hindrance, so the effect of preventing the aromatic rings from being closely adjacent to each other is large, and a film with a low film density can be provided. That is, by using this preferred aspect of the resist underlayer film-forming composition, a resist underlayer film with excellent processing resistance and better air permeability can be provided.
[0133] In the above formulae (I) and (II), R1 is a structure R selected from the group consisting of the groups shown in the following formula (III-1): 1-1 and a structure R selected from the group consisting of groups represented by the following formula (III-2): 1-2 Combination of structure R 1-1 The ratio is set to a, and the structure R 1-2 When the ratio of is set to b, it is ideal that the ratios a and b satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100.
[0134] [Chemistry 9]
[0135]
[0136] In formulae (III-1) and (III-2), * represents a bonding site to an oxygen atom.
[0137] In the above general formulae (I) and (II), R1 is a structure R selected from the group consisting of the groups shown in the above formula (III-1) from the viewpoint of maintaining processing resistance, reducing film density, and improving thermal fluidity. 1-1 Preferably, from the viewpoint of curability, the structure R is selected from the group consisting of the groups shown in the following formula (III-2): 1-2 Therefore, when the curability of the resin is insufficient, the structure R 1-1 and structure R 1-2 It is preferable to select one or more of them and use them in combination. 1-2 The hardness obtained is related to the structure R 1-1The balance of the effects obtained is more ideal in terms of the ratio of the combination of the substituent structures of these two groups, and the ratio is more ideal when the curability of the resin alone is guaranteed to the minimum. Specifically, it is more ideal to satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100, and it is more ideal to satisfy the relationship of 10≤b≤90 and a+b=100, and it is even more ideal to satisfy the relationship of 10≤b≤50 and a+b=100.
[0138] R1 can be a combination of at least two or more in the same resin, and n1 R1s in the same repeating unit structure may be all the same. By virtue of R1 being a combination of at least two or more in the same resin, the novolac resin contained in the resist underlayer film forming composition of the present invention may contain, for example, at least two repeating units with different OR1 in the same resin. Or, the novolac resin contained in the resist underlayer film forming composition of the present invention may contain repeating units containing two or more OR1 groups when n1 is 2 or more. By virtue of R1 being a combination of at least two or more in the same resin, thermal fluidity will be improved, flatness will be improved, and swelling (density reduction) of the film obtained from the composition after reworking can be achieved.
[0139] In the above general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted multiple aryl groups having 6 to 30 carbon atoms bonded to each other via a straight-chain, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. From the perspective of processing resistance, simple aromatic compounds such as benzene, naphthalene and anthracene are more preferred. With regard to Ar1, from the perspective of reducing the film density, structures formed by combining aryl groups bonded or condensed with straight-chain, branched or cyclic alkyl groups or ethers, such as compounds having a spirodihydroindane structure or a spirocyclic structure, resveratrol, hematoxylin, etc. are more preferred.
[0140] Ar1 may be one or a combination of multiple types in the same resin, and Ar2 may be one or a combination of multiple types in the same resin. By combining multiple types, the molecular weight during condensation can be adjusted, and the solubility and thermal fluidity of the condensate can be improved.
[0141] In the above general formulas (I) and (II), R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group with 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group with 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom, and they can be selected according to the desired properties. For example, from the perspective of thermal fluidity, a straight-chain, branched or cyclic hydrocarbon group or heteroalkyl group is more ideal, and from the perspective of maintaining processing resistance while suppressing the accumulation of aromatic rings, a cyclic hydrocarbon group is more ideal. In addition, from the perspective of thermal curing, it is more ideal to contain an unsaturated bond, and from the perspective of improving the hydrophobicity of the film, it is more ideal to contain a fluorine atom.
[0142] The specific structure of the core structure containing Ar1, R2, and OR1 in the general formulae (I) and (II) above includes the following structures, but is not limited thereto. Also, OR1 can be appropriately selected from the specific examples described above.
[0143] [Chemistry 10]
[0144]
[0145] [Chemistry 11]
[0146]
[0147] [Chemistry 12]
[0148]
[0149] [Chemistry 13]
[0150]
[0151] [Chemistry 14]
[0152]
[0153] The specific structure of the core structure containing Ar2, R2 and OR1 of the general formula (II) above includes the following structures, but is not limited thereto. Also, OR1 can be appropriately selected from the specific examples above. * is a bonding site with a trityl group.
[0154] [Chemistry 15]
[0155]
[0156] In the above general formulae (I) and (II), Ar1 is preferably selected from the group consisting of structures represented by the following formula (Ar-1) from the viewpoints of raw material availability, reactivity, and reduction in film density.
[0157] [Chemistry 16]
[0158]
[0159] In the above general formula (I) and (II), if Ar1 is a benzene ring or a naphthalene ring, the monomer itself is rich in variety, and substituents can be selected to reconcile various physical properties by matching the required performance. For example, when it is desired to suppress accumulation, alkyl groups such as tert-butyl and cyclohexyl can be selected, and when it is desired to make the film hydrophobic, fluorine atoms can be selected. In addition, the other structures shown in the above formula (Ar-1) all have 2 benzene rings in one molecule and they are bonded by straight-chain, cyclic alkyl, ether groups, or contracted, so a structure that can suppress the accumulation of aromatic rings can be formed, and the film after baking can be suppressed from becoming high-density. Therefore, good air permeability will be exhibited, and the resist lower layer film with good flatness will also be obtained.
[0160] In the above general formula (II), Ar2 is preferably a benzene ring from the viewpoint of raw material availability and reactivity.
[0161] In the above formula (II), when Ar2 is a benzene ring, various raw materials having different substituents can be obtained, so that the physical properties can be adjusted in accordance with the required performance.
[0162] In general formulae (I) and (II), n1 is an integer greater than 1, and n2, n3, and n4 are integers greater than 0. n1 is preferably 2 or greater from the viewpoint of reducing film density and increasing thermal fluidity. n2 is preferably 0 from the viewpoint of polymerizability, and is preferably 1 to 2 from the viewpoint of reducing film density and increasing thermal fluidity. n3 and n4 are preferably 1 or greater from the viewpoint of reducing film density and increasing thermal fluidity.
[0163] Then, in the above formula (II), n3+n4 is preferably an integer greater than 2, and the preferred specific structure of the core structure containing Ar2, R2, and OR1 includes the following structures. In addition, OR1 can be appropriately selected from the above specific examples. * is the bonding site with the trityl group.
[0164] [Chemistry 17]
[0165]
[0166] The resist underlayer film forming composition of the present invention only needs to contain at least one of a novolac resin having a repeating unit structure represented by the general formula (I) and a novolac resin having a repeating unit structure represented by the general formula (II). It may contain either a novolac resin having a repeating unit structure represented by the general formula (I) or a novolac resin having a repeating unit structure represented by the general formula (II), or both. Furthermore, it may contain a novolac resin having both a repeating unit structure represented by the general formula (I) and a repeating unit structure represented by the general formula (II). On the other hand, the novolac resin contained in the resist underlayer film forming composition of the present invention may contain two or more of the above-mentioned repeating unit structures whose R1 is different from each other.
[0167] <(A) Synthesis method of novolac resin>
[0168] The above-mentioned (A) novolac resin is usually synthesized by using a derivative (X) of Ar1 containing a hydroxyl group, a benzaldehyde derivative (Y) containing formaldehyde or Ar2, and a catalyst to carry out a condensation reaction (STEP 1 shown below), and then etherifying the obtained condensate using a halogenated alkyl, an alkyl p-toluenesulfonate or an alkyl methanesulfonate (Z) and a catalyst (STEP 2 shown below). (R1, R2, n1, n2, n3, and n4 are the same as those described above, X is a halogen group, a methanesulfonyl group or a p-toluenesulfonyl group, and R1-X uses two or more types, but only one type is described in the description.
[0169] [Chemistry 18]
[0170]
[0171] [Chemistry 19]
[0172]
[0173] The condensation reaction using the hydroxyl-containing Ar1 derivative (X), formaldehyde or benzaldehyde derivative (Y), and a catalyst can usually be carried out without a solvent or using an acid or base as a catalyst in a solvent, and at room temperature or under cooling or heating as needed.
[0174] Examples of the solvent include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; lactones such as γ-butyrolactone; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, and hexamethylphosphoramide. These solvents may be used alone or in combination of two or more. These solvents can be used in an amount within a range of 0 to 3000 parts by mass based on 100 parts by mass of the reaction raw materials.
[0175] As the acid catalyst used, inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids, organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid, aluminum trichloride, aluminum triethoxide, aluminum isopropoxide, boron trifluoride, boron trichloride, boron tribromide, tin tetrachloride, tin tetrabromide, dibutyltin dichloride, dibutyldimethoxytin, dibutyltin oxide, titanium tetrachloride, titanium tetrabromide, titanium (IV) tetramethoxide, titanium (IV) tetraethoxide, titanium (IV) tetraisopropoxide, and titanium (IV) oxide can be used. Lewis acids As the base catalyst used, inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, calcium hydride, etc., alkyl metals such as methyl lithium, n-butyl lithium, methyl magnesium chloride, ethyl magnesium bromide, etc., alkoxides such as sodium methoxide, sodium ethoxide, potassium tert-butoxide, and organic bases such as triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, 4-dimethylaminopyridine, etc. can be used. The amount used is 0.001 to 100% by weight, preferably 0.005 to 50% by weight, relative to the raw material.
[0176] The reaction temperature is preferably from -50°C to about the boiling point of the solvent, and more preferably from room temperature to 130°C.
[0177] As for the condensation reaction method, there are methods of feeding the hydroxyl-containing Ar1 derivative (X), formaldehyde or benzaldehyde derivative (Y), and catalyst all at once; a method of dripping formaldehyde or benzaldehyde derivative (Y) or a solution obtained by dissolving formaldehyde or benzaldehyde derivative (Y) in a reaction solvent in the presence of the derivative (X) and the catalyst; a method of dripping the derivative (X) or a solution obtained by dissolving the derivative (X) in a reaction solvent in the presence of formaldehyde or benzaldehyde derivative (Y) and the catalyst, etc. At this time, the amount of formaldehyde or benzaldehyde derivative (Y) used is preferably 0.7 to 1.2 equivalents relative to the derivative (X), and more preferably 0.8 to 1.05 equivalents. After the condensation reaction is terminated, in order to remove the unreacted raw materials, catalysts, etc. in the system, the temperature of the reactor can be raised to 130-230°C and the volatile components can be removed at about 1-50 mmHg, according to the raw materials used and the properties of the obtained reaction product; a method of adding an appropriate poor solvent or water to reprecipitate the polymer; a method of classifying the polymer, etc. The obtained condensate can also be dissolved in an appropriate solvent that does not mix with water, such as methyl isobutyl ketone, ethyl acetate, and then washed with water.
[0178] The subsequent etherification can be generally carried out without a solvent or using a base as a catalyst in a solvent at room temperature or, if necessary, under cooling or heating. Examples of the solvent include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; lactones such as γ-butyrolactone; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoramide, and N-methylpyrrolidone. These solvents may be used alone or in combination of two or more.
[0179] These solvents can be used in an amount within a range of 0 to 2,000 parts by mass based on 100 parts by mass of the reaction raw materials.
[0180] As the base catalyst used, inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, calcium hydride, etc., alkyl metals such as methyl lithium, n-butyl lithium, methyl magnesium chloride, ethyl magnesium bromide, etc., alkoxides such as sodium methoxide, sodium ethoxide, potassium tert-butoxide, triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, 4-dimethylaminopyridine, etc. can be used. The amount used is preferably 0.5 to 1.5 equivalents, more preferably 1.0 to 1.2 equivalents, relative to the equivalent of the hydroxyl group contained in the raw material of the condensation reaction.
[0181] The reaction temperature is preferably from -50°C to the boiling point of the solvent, and more preferably from room temperature to 130°C.
[0182] As for the reaction method of (STEP2), the above-mentioned condensation product includes a method of feeding the compound (Z) and the catalyst at one time; a method of adding the compound (Z) or a solution obtained by dissolving the compound (Z) in a reaction solvent dropwise in the presence of the above-mentioned condensation product and the catalyst; and a method of adding the above-mentioned condensation product dissolved in a reaction solvent dropwise in the presence of the compound (Z) and the catalyst. In addition, the synthesis of the compound of the present invention uses a plurality of compounds (Z), so the reaction can be carried out by appropriately combining the following methods: a method in which a compound (Z) having a large steric hindrance and low reactivity at the reaction site such as bromomethylcyclohexane is first added dropwise in the presence of the above-mentioned condensate and the catalyst, and then ripened, and then a compound (Z) having a small steric hindrance and high reactivity at the reaction site such as propargyl bromide is added; a method in which a high-boiling point compound (Z) such as bromomethylcyclohexane, methanesulfonyl group, p-toluenesulfonyl group which cannot be removed under reduced pressure after the reaction, or a solution thereof dissolved in a reaction solvent is first added dropwise and ripened, and then a slightly excess amount of a low-boiling point compound (Z) such as propargyl bromide and allyl bromide which can be removed under reduced pressure after the reaction is added dropwise to increase the substitution rate, etc. After the etherification is terminated, in order to remove the unreacted raw materials, catalysts, etc. in the system, there are the following methods: a method of raising the temperature of the reactor to 130-230°C and removing the volatile components under the condition of about 1-50 mmHg; a method of adding an appropriate poor solvent or water to reprecipitate the polymer; a method of classifying the polymer, etc.; these methods can be flexibly used according to the properties of the obtained reaction product. In addition, a step of removing metal species such as sodium and potassium by dissolving the finally obtained novolac resin in an appropriate solvent that is not miscible with water, such as methyl isobutyl ketone and ethyl acetate, and then performing acid washing with an appropriate acid such as nitric acid and hydrochloric acid or washing with ultrapure water can be added.
[0183] The polystyrene-equivalent weight average molecular weight Mw of the novolac resin (A) obtained by the above-mentioned synthesis method, for example, measured by gel permeation chromatography is preferably 2,000 to 8,000, more preferably 2,000 to 6,000, from the viewpoint of embedding properties and suppression of sublimates.
[0184] If the weight average molecular weight Mw of the novolac resin (A) is 2000-8000, the low molecular weight components that become sublimates during baking will be reduced, so that poor film forming properties can be suppressed and an underlayer film without impairing the filling properties can be formed. If it is 2000-6000, this effect will be further enhanced.
[0185] <(B) Organic Solvent>
[0186] Furthermore, as for the organic solvent (B) that may be used, there are no particular restrictions as long as it can dissolve the above-mentioned (A) phenolic varnish resin and any components contained therein, such as (C) surfactants, (D) crosslinking agents, (E) thermally decomposable resins, (F) acid generators (e.g., thermal acid generators), other additives, etc., as described later.
[0187] Specifically, an organic solvent described in paragraphs
[0091] to
[0092] of Japanese Patent Application Laid-Open No. 2007-199653 may be added. More specifically, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, cyclohexanone and γ-butyrolactone, or a mixture containing one or more of these may be preferably used.
[0188] The amount of the organic solvent to be added is preferably in the range of 200 to 10,000 parts, more preferably 250 to 5,000 parts, based on 100 parts by mass of the novolac resin (A).
[0189] In the resist underlayer film forming composition of the present invention, as for the aforementioned (B) organic solvent, a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher ((B2) high boiling point solvent) may be used.
[0190] The high boiling point solvent (B2) is not particularly limited to hydrocarbons, alcohols, ketones, esters, ethers, chlorine-based solvents, etc. as long as it can dissolve the components of the resist underlayer film forming composition of the present invention. Specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, and 2,4-heptanediol. , 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol di Methyl ether, triethylene glycol monomethyl ether, triethylene glycol-n-butyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol diacetate , dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc., which can be used alone or in combination.
[0191] The high boiling point solvent can be appropriately selected from, for example, the above-mentioned ones according to the temperature at which the resist lower film forming composition of the present invention is subjected to heat treatment. The boiling point of the high boiling point solvent is preferably 180°C to 300°C, and more preferably 200°C to 300°C. It is believed that if this boiling point is used, there will be no risk of volatilization becoming too fast during baking (heat treatment), so sufficient thermal fluidity can be obtained during film formation, and a resist lower film with excellent embedding / planarization characteristics can be formed. In addition, if this boiling point is used, it will not remain in the film without volatilization after baking, so there will be no risk of adversely affecting the film properties such as embedding characteristics.
[0192] When a high boiling point solvent is used, the blending amount is preferably set to 1 to 30 parts by mass relative to 100 parts by mass of the organic solvent having a boiling point of less than 180° C. Such a blending amount is preferred because it can provide sufficient thermal fluidity during baking, does not remain in the film, and does not contribute to the deterioration of the film properties such as the landfill characteristics.
[0193] <Optional Ingredients>
[0194] The resist underlayer film-forming composition of the present invention may further contain an optional component other than the above-mentioned (A) novolac resin and the above-mentioned (B) organic solvent.
[0195] <(C) Surfactant>
[0196] The composition of the present invention may also contain (C) a surfactant. To the resist underlayer film-forming composition of the present invention, a surfactant (C) may be added in order to improve coating properties during spin coating.
[0197] As the surfactant, for example, those described in
[0142] to
[0147] of JP-A-2009-269953 can be used. The amount of the surfactant added is preferably 0.01 to 10 parts, more preferably 0.05 to 5 parts, based on 100 parts by mass of the (A) novolac resin.
[0198] <(D) Cross-linking agent>
[0199] The composition of the present invention may also contain a crosslinking agent (D). The crosslinking agent (D) promotes crosslinking within the film, and because of its structure containing an aromatic ring, it is closely adjacent to the novolac resin (A), which has the effect of increasing the density of the film. Therefore, there are fewer holes such as those impregnated with the solvent, and the swelling of the film after reworking is suppressed. Therefore, the crosslinking agent can be added as a crosslinking accelerator and a swelling inhibitor of the film.
[0200] As for the crosslinking agent (D), there is no particular limitation, and various well-known crosslinking agents can be widely used. For example, melamine crosslinking agents, acrylate crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, epoxy crosslinking agents, phenol crosslinking agents (such as hydroxymethyl or alkoxymethyl crosslinking agents of polynuclear phenols) can be exemplified. The content of the crosslinking agent (D) is preferably 5 to 50 parts by mass, and more preferably 10 to 40 parts by mass, relative to 100 parts by mass of the novolac resin (A).
[0201] Specific examples of the melamine-based crosslinking agent include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy and / or hydroxyl-substituted melamines thereof, and partial self-condensates thereof.
[0202] Specific examples of the acrylate crosslinking agent include dipentatriol hexaacrylate.
[0203] Specific examples of glycoluril-based crosslinking agents include tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensation products thereof.
[0204] Specific examples of the benzoguanamine-based crosslinking agent include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensed products thereof.
[0205] Specific examples of the urea crosslinking agent include dimethoxymethylated dimethoxyethylene urea, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensates thereof.
[0206] Specific examples of the β-hydroxyalkylamide crosslinking agent include N,N,N′,N′-tetrakis(2-hydroxyethyl)adipamide.
[0207] Specific examples of the isocyanurate-based crosslinking agent include triglycidyl isocyanurate and triallyl isocyanurate.
[0208] Specific examples of the aziridine crosslinking agent include 4,4′-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate].
[0209] Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers.
[0210] Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0211] Specific examples of the polynuclear phenol crosslinking agent include compounds represented by the following general formula (XL-1).
[0212] [Chemistry 20]
[0213]
[0214] In the formula, L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R3 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. q is an integer of 1 to 5.
[0215] L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. Q is an integer of 1 to 5, and is more preferably 2 or 3. As for L, specifically, there can be exemplified a group formed by removing q hydrogen atoms from methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane. R3 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. As for the alkyl group having 1 to 20 carbon atoms, specifically, there can be exemplified a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, an isopentyl group, a hexyl group, an octyl group, an ethylhexyl group, a decyl group, and an eicosyl group, and is preferably a hydrogen atom or a methyl group.
[0216] As for the examples of the compounds represented by the general formula (XL-1), the following compounds can be specifically exemplified. Among them, hexamethoxymethylated forms of trisphenolmethane, trisphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are particularly preferred from the viewpoint of improving the hardening property and film thickness uniformity of the organic film. R3 is the same as described above.
[0217] [Chemistry 21]
[0218]
[0219] [Chemistry 22]
[0220]
[0221] <(E) Thermally Decomposable Resin>
[0222] Furthermore, the resist underlayer film forming composition of the present invention may contain (E) a thermally decomposable resin from the viewpoint of reducing the film density.
[0223] As the (E) pyrolyzable resin, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a pyrolyzable polymer (resin) having a weight loss rate of 40% by mass or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000 can be preferably used. The pyrolyzable polymer preferably contains a repeating unit having an acetal structure represented by the following general formulae (DP1), (DP1a) to (DP3a).
[0224] [Chemistry 23]
[0225]
[0226] In the formula, R 1 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. W is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.
[0227] [Chemistry 24]
[0228]
[0229] In formulas (DP1a) to (DP3a), R 1a W is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may have an ether bond. b1 Each independently is -W a -OH, or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms; 1c R is a hydrogen atom, or an optionally substituted aryl group having 6 to 20 carbon atoms, or a heteroaryl group having 4 to 20 carbon atoms. c1 are each independently an alkyl group having 1 to 4 carbon atoms, or -W a -OH. n represents the average number of repeating units, which is 3 to 500.
[0230] Specific examples of the thermally decomposable resin include those shown below, but are not limited to these.
[0231] [Chemistry 25]
[0232]
[0233] [Chemistry 26]
[0234]
[0235] [Chemistry 27]
[0236]
[0237] [Chemistry 28]
[0238]
[0239] n represents an average repeating unit, and is 3 or more and 500 or less.
[0240] The amount of the (E) thermally decomposable resin added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the (A) novolac resin.
[0241] <(F) Acid Generator>
[0242] In order to further promote the curing reaction of the novolac resin (A), an acid generator may be added to the resist underlayer film forming composition of the present invention. Acid generators may be those that generate acid by thermal decomposition (thermal acid generators) or those that generate acid by light irradiation (photoacid generators), and both may be added. Specifically, materials described in paragraphs
[0061] to
[0085] of Japanese Patent Application Publication No. 2007-199653 may be added, but are not limited to these.
[0243] The acid generator may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the novolac resin (A).
[0244] [Physical properties related to film density]
[0245] The composition for forming an anti-etching underlayer film of the present invention, for example, when the composition for forming an anti-etching underlayer film of the present invention is applied to a substrate to obtain a coating film, the coating film is calcined at 180°C for 60 seconds, and then additionally calcined at 350°C for 60 seconds, the film thickness of which is defined as FT-1, and after the additional calcination, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is configured on the coating film, followed by allowing to stand for 30 seconds, the coating film is spin-dried, and then the coating film is baked at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2, which can be 100.5<{(FT-2) / (FT-1)}×100.
[0246] {(FT-2) / (FT-1)}×100 is greater than 100.5, which means that the film swells after reworking and becomes a porous film with fine pores as if the solvent is impregnated. If a dense hardening reaction occurs like a normal resin, there will be no gaps for the solvent to be impregnated, so this kind of swelling will not occur, and the film thickness will not become extremely thick after reworking. Based on the above experience, the inventors of this application believe that the composition of the present invention is a porous film as if the solvent is impregnated, the film density becomes low, and the gas will seep out of the film and penetrate like the solvent.
[0247] If 100.5 < {(FT-2) / (FT-1)} × 100, it means that the calcined membrane will become a porous membrane with a large number of pores such as the OK73 diluent can penetrate, and the larger the value, the more porous and low-density the membrane. Therefore, considering the air permeability, it is more ideal to be 101 < {(FT-2) / (FT-1)} × 100.
[0248] When the crosslinking agent (D) is further included, the composition is preferably 100<{(FT-2) / (FT-1)}×100<101. As previously mentioned, the crosslinking agent (D) has the effect of increasing the density of the membrane. Therefore, there are fewer holes such as those impregnated with the solvent, and the swelling of the membrane after reworking is suppressed. Therefore, the crosslinking agent can be added as a crosslinking accelerator and a swelling inhibitor of the membrane.
[0249] When (E) a pyrolyzable resin is further included, it is more ideal to be 101<{(FT-2) / (FT-1)}×100. By including (E) a pyrolyzable resin, the pyrolyzable resin decomposes during baking and sublimates from the film, thereby forming tiny pores in the film. Therefore, the swelling of the film after reworking becomes larger, so the porosity of the film is increased, and the film density can be reduced.
[0250] When both (D) a crosslinking agent and (E) a thermally decomposable resin are contained, it is also preferable that the ratio is 100<{(FT-2) / (FT-1)}×100.
[0251] (D) Crosslinking agent and (E) thermally decomposable resin have opposite effects as density adjusters of the film, so when both are contained at the same time, as long as the curing of the film can be confirmed, when comparing the difference in film thickness before and after reworking, it is sufficient to achieve (FT-2)>(FT-1).
[0252] Hereinafter, a method for producing a resist underlayer film, a method for forming a pattern, and a method for producing a semiconductor device using the resist underlayer film-forming composition of the present invention will be described.
[0253] [Method for producing resist underlayer film]
[0254] The method for manufacturing the resist underlayer film of the present invention comprises the following steps:
[0255] The resist underlayer film forming composition of the present invention is applied on a semiconductor substrate to obtain a coating film,
[0256] The coated film is fired to obtain a resist underlayer film.
[0257] Semiconductor substrates, such as substrates used in the manufacture of semiconductor devices, such as silicon wafer substrates, silicon / silicon dioxide coated substrates, silicon nitride substrates, glass substrates, ITO substrates, polyimide substrates, and low dielectric constant material (low-k material) coated substrates.
[0258] The resist underlayer film forming composition of the present invention is applied onto the semiconductor substrate by an appropriate coating method such as a spinner or a coater to obtain a coating film.
[0259] Thereafter, the coated film is fired to form a resist underlayer film.
[0260] As for the calcination conditions, it can be appropriately selected from the calcination temperature of 80°C to 400°C and the calcination time of 0.3 to 60 minutes. It is more ideal to have a calcination temperature of 150°C to 350°C and a calcination time of 0.5 to 2 minutes. It is more ideal to have a two-stage calcination of calcination at a calcination temperature of 100°C to 200°C and 0.5 to 2 minutes, and then to have additional calcination at 200°C to 350°C and 0.5 to 2 minutes. Here, as for the film thickness of the formed lower film, for example, 10 to 1500nm, more preferably 500 to 1000nm. In addition, if a quartz substrate is used as a substrate, a replica of a quartz imprint mold (mold replica) can be made.
[0261] In addition, a close-contact layer and / or a polysilicon oxide layer containing less than 99% by mass or less than 50% by mass Si can be formed by coating or vapor deposition on the resist lower film formed as above. For example, the close-contact layer recorded in Japanese Unexamined Patent Publication No. 2013-202982 and Japanese Patent No. 5827180, except the method of forming the silicon-containing resist lower film (inorganic resist lower film) recorded in WO2009 / 104552A1 into a composition by spin coating, can be formed by the inorganic material film of Si system with CVD method etc.
[0262] Furthermore, the resist underlayer film forming composition of the present invention can form an underlayer film showing improved flatness as described above. For example, the resist underlayer film forming composition of the present invention is applied to a semiconductor substrate having a portion with a height difference and a portion without a height difference (so-called a height difference substrate) to obtain a coating film, and the coating film is calcined to form a resist underlayer film in which the height difference between the portion with a height difference and the portion without a height difference falls within a range of 3 to 100 nm.
[0263] [Pattern Formation Method]
[0264] The pattern forming method of the present invention comprises the following steps:
[0265] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0266] forming a hardening composition film on the resist underlayer film,
[0267] The curable composition film is brought into contact with a mold,
[0268] The curable composition film is irradiated with light or electron beam to form a cured film.
[0269] The cured film is separated from the mold.
[0270] This pattern forming method is called an imprint method using a mold. The imprint method may also be a nanoimprint method. By using the pattern forming method using the imprint method of the present invention, it is possible to utilize a resist underlayer film that has good processing tolerance, excellent filling and flatness, low film density, and good air permeability. Therefore, by using the pattern forming method using the imprint method of the present invention, it is possible to quickly remove bubbles generated when the mold is pressed against the curable composition film, and to form a fine pattern.
[0271] Hereinafter, each step will be described in more detail.
[0272] <Step of Forming Resist Underlayer Film>
[0273] In this step, for example, a resist underlayer film can be formed on a semiconductor substrate from the resist underlayer film-forming composition of the present invention by the method for producing a resist underlayer film of the present invention described above.
[0274] <Step of Forming a Curable Composition Film>
[0275] This step is a step of forming a curable composition film on the resist underlayer film.
[0276] The composition of the curable composition film formed on the resist underlayer film is not particularly limited as long as it is photosensitized for use in exposure. Both negative photoresists and positive photoresists can be used. There are positive photoresists composed of novolac resin and 1,2-naphthoquinonediazide sulfonate, chemically amplified photoresists composed of a binder and a photoacid generator having a group that decomposes due to acid and increases the alkali dissolution rate, chemically amplified photoresists composed of a low molecular compound that decomposes due to acid and increases the alkali dissolution rate of the photoresist, an alkali-soluble binder, and a photoacid generator, and chemically amplified photoresists composed of a binder having a group that decomposes due to acid and increases the alkali dissolution rate, a low molecular compound that decomposes due to acid and increases the alkali dissolution rate of the photoresist, and a photoacid generator. Examples include APEX-E manufactured by Shipley, PAR710 manufactured by Sumitomo Chemical, and SEPR430 manufactured by Shin-Etsu Chemical. In addition, examples include fluorine-containing polymer photoresists described in Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).
[0277] [Method of using the curable composition]
[0278] As for the method of applying the curable composition, inkjet method, dip coating method, air knife coating method, curtain coating method, wire rod coating method, gravure coating method, extrusion coating method, spin coating method, slit scanning method, etc. can be used. In order to apply the curable composition in the form of droplets, the inkjet method is suitable, and in order to apply the curable composition, the spin coating method is suitable. In this step, a close contact layer and / or a polysilicon layer containing 99% by mass or less, or 50% by mass or less of Si can also be formed by coating or evaporation on the resist lower film for nanoimprinting, and the curable composition is applied thereon.
[0279] In the step of forming the curable composition film, an adhesion layer and / or a polysilicon layer containing 99 mass % or less of Si may be formed on the resist underlayer film by coating or vapor deposition.
[0280] By forming the adhesion layer, the pattern peeling can be sufficiently suppressed in the subsequent step of separating the mold. In addition, by forming a polysilicon layer containing 99 mass % or less of Si, the optical properties of the film can be adjusted, and reflection control can be achieved.
[0281] <Step of bringing the curable composition film into contact with the mold>
[0282] In this step, the curable composition film is brought into contact with the mold. For example, if the curable composition film as a liquid is brought into contact with the mold having a prototype pattern for transferring the pattern shape, the curable composition fills the concave portions of the fine pattern on the surface of the mold to form a liquid film.
[0283] Considering the step of irradiating light or electron beams described later, it is recommended to use a mold with a light-transmitting material as the base material. Specifically, the mold base material is preferably glass, quartz, PMMA, light-transparent resins such as polycarbonate resin, transparent metal vapor-deposited films, soft films such as polydimethylsiloxane, light-curing films, metal films, etc. Quartz is the most ideal mold base material because it has a small thermal expansion coefficient and small pattern strain.
[0284] The fine pattern on the surface of the mold preferably has a pattern height of 4 nm or more and 200 nm or less. In order to improve the processing accuracy of the substrate, a certain degree of pattern height is necessary, but if the pattern height is low, the force required to peel the mold from the cured film in the step of separating the cured film from the mold described later is low, and the number of defects remaining on the mask side due to the resist pattern being torn apart is small. It is recommended to select and adopt an appropriately balanced pattern height in consideration of these.
[0285] In addition, due to the impact of stripping the mold, the elastic deformation of the resist pattern causes the adjacent resist patterns to contact each other, which may cause the resist pattern to stick or break. This can be avoided by setting the pattern height to less than about 2 times the pattern width (aspect ratio less than 2).
[0286] In order to improve the releasability of the curable composition from the surface of the mold, the mold may also be surface treated in advance. As for the surface treatment method, a method such as coating a release agent on the surface of the mold to form a release agent layer can be cited. As for the release agent, examples include silicone release agents, fluorine release agents, hydrocarbon release agents, polyethylene release agents, polypropylene release agents, paraffin release agents, lignite release agents, palm release agents, etc. are listed. Fluorine and hydrocarbon release agents are more ideal. As for commercial products, for example, there are OPTOOL (registered trademark) DSX made by Daikin Industries (stock). A release agent can be used alone, or two or more can be used in combination.
[0287] In this step, when the mold is brought into contact with the curable composition, the pressure applied to the curable composition is not particularly limited. A pressure of 0 MPa or more and 100 MPa or less is recommended. The pressure is preferably 0 MPa or more and 50 MPa or less, 30 MPa or less, or 20 MPa or less.
[0288] When the liquid droplets of the curable composition are pre-applied in the previous step (the step of applying the curable composition), the application of the curable composition in this step is quickly completed. As a result, the contact time between the mold and the curable composition can be shortened. The contact time is not particularly limited, but is preferably 0.1 seconds or more and 600 seconds or less, 3 seconds or less, or 1 second or less. If the contact time is too short, the application and filling are insufficient, and there is a risk of a defect called an unfilled defect.
[0289] This step can be performed under any of the following conditions: atmospheric gas environment, reduced pressure gas environment, and inert gas environment. It is preferably performed under a pressure of 0.0001 atmospheres or more and 10 atmospheres or less. In order to prevent the influence of oxygen and moisture on the curing reaction, it is recommended to perform the step under a reduced pressure gas environment or an inert gas environment. Specific examples of inert gases that can be used to create an inert gas environment include nitrogen, carbon dioxide, helium, argon, CFC, HCFC, HFC, or a mixture thereof.
[0290] This step can also be performed in a gas environment containing condensable gas (hereinafter referred to as "condensable gas environment"). The so-called condensable gas in this specification refers to a gas that will condense and liquefy due to the capillary pressure generated during filling when it is filled in the recesses of the fine pattern formed on the mold and the gap between the mold and the substrate together with the curable composition. In addition, the condensable gas exists in the form of gas in the gas environment before the curable composition contacts the mold in this step. If this step is performed in a condensable gas environment, the gas filled in the recesses of the fine pattern will be liquefied by the capillary pressure generated by the curable composition, thereby eliminating bubbles, so the filling property is excellent. Condensable gas can also be dissolved in the curable composition.
[0291] The boiling point of the condensable gas is not limited as long as it is lower than the gas environment temperature in this step, but is preferably -10°C or higher, or +10°C or higher and +23°C or lower.
[0292] The vapor pressure of the condensable gas at the gas atmosphere temperature in this step is not particularly limited as long as it is equal to or lower than the mold pressure, but is preferably in the range of 0.1 MPa to 0.4 MPa.
[0293] Specific examples of condensable gases include chlorofluorocarbons (CFCs) such as trichlorofluoromethane, fluorocarbons (FCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs) such as 1,1,1,3,3-pentafluoropropane (CHF2CH2CF3, HFC-245fa, PFP), and hydrofluoroethers (HFEs) such as pentafluoroethyl methyl ether (CF3CF2OCH3, HFE-245mc).
[0294] The condensable gas may be used alone or in a mixture of two or more. These condensable gases may also be mixed with non-condensable gases such as air, nitrogen, carbon dioxide, helium, and argon. As for the non-condensable gas mixed with the condensable gas, air and helium are more preferable.
[0295] <Step of irradiating the curable composition film with light or electron beam to form a cured film>
[0296] In this step, the curable composition film is irradiated with light or electron beams to form a cured film. That is, the curable composition film filled in the fine pattern of the mold is irradiated with light or electron beams through the mold, and the curable composition filled in the fine pattern of the mold is directly cured in this state, thereby forming a cured film having a pattern shape.
[0297] The light or electron beam is selected according to the sensitivity wavelength of the curable composition. Specifically, ultraviolet light, X-rays, electron beams, etc. with a wavelength of more than 150nm and less than 400nm can be appropriately selected and used. As for the light source of the light or electron beam, there can be listed high-pressure mercury lamps, ultra-high-pressure mercury lamps, low-pressure mercury lamps, Deep-UV lamps, carbon arc lamps, chemical lamps, metal halide lamps, xenon lamps, KrF excimer lasers, ArF excimer lasers, F2 excimer lasers, etc. The number of light sources can be 1 or plural. Irradiation can be performed on the entire curable composition filled in the fine pattern of the mold, or only on a part of the area. Light irradiation can be performed intermittently multiple times on all areas on the substrate, or it can be continuously irradiated on all areas. In addition, a part of the area on the substrate can be irradiated for the first time, and then a second irradiation can be performed on a different area from the area.
[0298] The cured film obtained in this manner preferably has a pattern having a size of 1 nm or more, or 10 nm or more, and 10 mm or less, or 100 μm or less.
[0299] <Steps for separating the cured film from the mold>
[0300] In this step, the cured film is separated from the mold. By pulling the cured film having the pattern shape away from the mold, a cured film having a pattern shape that is a reverse pattern of the fine pattern formed on the mold can be obtained in a self-supporting state.
[0301] As for the method of separating the cured film having a pattern shape from the mold, if it is a means to move the cured film and the mold in a direction of relative separation, there is no particular limitation as long as a part of the cured film having a pattern shape is not physically damaged, and there is no particular limitation on various conditions. For example, the substrate may be fixed and the mold may be moved away from the substrate to be peeled off, or the mold may be fixed and the substrate may be moved away from the mold to be peeled off. Alternatively, the substrate and the mold may be pulled apart and moved in opposite directions to be peeled off.
[0302] In addition, when the step of bringing the curable composition into contact with the mold is performed under a condensable gas environment, when the cured film is separated from the mold in this step, the condensable gas is vaporized as the pressure at the interface between the cured film and the mold decreases. This can reduce the demolding force, which is the force required to separate the cured film from the mold.
[0303] By the above steps, a cured film having a desired concavo-convex pattern shape derived from the concavo-convex shape of the mold at a desired position can be prepared.
[0304] In addition, the pattern forming method using the imprint method has been described above, but the resist underlayer film obtained by the resist underlayer film forming composition of the present invention is not limited to the pattern forming method using the imprint method. For example, it can also be used as a resist underlayer film in a pattern forming method for a multilayer resist process.
[0305] [Method for manufacturing semiconductor device]
[0306] A method for manufacturing a semiconductor device according to a first aspect of the present invention comprises the following steps:
[0307] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0308] forming a resist film on the resist underlayer film,
[0309] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0310] Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film,
[0311] The semiconductor substrate is processed using the patterned underlayer film as a mask.
[0312] Furthermore, a method for manufacturing a semiconductor device according to a second aspect of the present invention comprises the following steps:
[0313] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,
[0314] forming a hard mask on the resist underlayer film,
[0315] Then, a resist film is formed on the hard mask film.
[0316] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0317] The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask,
[0318] Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film,
[0319] The semiconductor substrate is processed using the patterned resist underlayer film as a mask.
[0320] Hereinafter, the method for manufacturing a semiconductor device according to the first aspect and the method for manufacturing a semiconductor device according to the second aspect will be described in detail in sequence.
[0321] <First Aspect>
[0322] [Step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film-forming composition of the present invention]
[0323] In this step, for example, the resist underlayer film can be formed by the method for producing a resist underlayer film of the present invention described above.
[0324] [Step of forming a resist film on the resist underlayer film]
[0325] Next, a step of forming a resist film on the resist underlayer film is performed.
[0326] The material of the resist film is not particularly limited as long as it is a resist material that can be used in the multilayer resist method.
[0327] [Step of irradiating the resist film with light or electron beams and then developing the resist film to form a resist pattern]
[0328] Next, the resist film formed in the above manner is irradiated with light or electron beams and then developed to form a resist pattern.
[0329] The light or electron beam irradiated can be appropriately selected according to the characteristics of the resist film. The method of development is not particularly limited as long as it can be used in the multilayer resist method.
[0330] [Step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film]
[0331] Next, the resist underlayer film is etched using the previously formed resist pattern as a protective film.
[0332] The etching in this step is preferably performed under conditions that make it easier to etch the resist underlayer film than the resist film. For example, when the resist film contains a large amount of silicon atoms, the resist film is not easily removed in dry etching using an oxygen-based gas, and the resist underlayer film is preferentially etched, so it is more ideal to perform dry etching using an oxygen-based gas.
[0333] Through this step, a patterned lower layer film can be obtained.
[0334] [Step of processing the semiconductor substrate using the patterned lower layer film as a mask]
[0335] Next, a step of processing the semiconductor substrate using the patterned lower layer film as a mask is performed.
[0336] Semiconductor substrate processing is preferably performed by dry etching using a fluorine-based gas.
[0337] Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).
[0338] <Second Aspect>
[0339] The second aspect is different from the first aspect in the steps of forming a hard mask on the resist underlayer film, etching the hard mask using the resist pattern as a mask, and etching the resist underlayer film using the patterned hard mask. The second aspect will be described below, centering on the differences from the first aspect.
[0340] The material of the hard mask is not particularly limited as long as it is a material of the hard mask that can be used in a multilayer resist process.
[0341] In the etching of the inorganic hard mask, for example, dry etching can be used. In the dry etching of the inorganic hard mask, for example, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride and chlorine trifluoride, chlorine, trichloroborane and dichloroborane can be used. It is ideal to use halogen gas in the dry etching of the inorganic hard mask, and it is more ideal to use fluorine gas. As for fluorine gas, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2) can be listed.
[0342] As in the second aspect, in the present invention, after forming a resist underlayer film on a substrate, a hard mask film is formed thereon, and then a resist film is coated thereon, whereby the pattern width of the resist film becomes narrower, and even when the resist film is coated thinly to prevent pattern collapse, the substrate can still be processed by selecting an appropriate etching gas. For example, a fluorine-based gas having a very fast etching rate for the resist film can be used as an etching gas to process the hard mask, a fluorine-based gas having a very fast etching rate for the hard mask can be used as an etching gas to process the resist underlayer film, and an oxygen-based gas having a very fast etching rate for the resist underlayer film can be used as an etching gas to process the substrate.
[0343] In any of the first and second aspects, an organic anti-reflection film may be formed on the upper layer of the resist underlayer film before forming the resist film or the hard mask. There is no particular limitation on the anti-reflection film composition used, and any composition conventionally used in the photolithography process may be selected and used. The anti-reflection film may be formed by conventional methods such as coating and calcination using a spinner or a coater.
[0344] The resist underlayer film formed by the resist underlayer film forming composition of the present invention may sometimes absorb the light used in the photolithography process depending on the wavelength of the light. In addition, at this time, it can function as an anti-reflection film having the effect of preventing reflected light from the substrate. Then, the underlayer film formed by the resist underlayer film forming composition of the present invention can function as a hard mask in the first embodiment. The underlayer film of the present invention can also be used as: a layer for preventing the interaction between the substrate and the resist film, a layer having the function of preventing the material used in the resist film or the substance generated during the exposure of the resist film from having a bad influence on the substrate, a layer having the function of preventing the diffusion of substances generated from the substrate to the resist film during heating and calcination, and a barrier layer for reducing the poisoning effect of the resist film caused by the dielectric layer of the semiconductor substrate, etc.
[0345] Furthermore, the underlayer film formed by the resist underlayer film forming composition of the present invention can be used as a filling material capable of filling the via hole without gaps in a substrate formed with via holes used in a dual metal damascene process, and can also be used as a planarizing material for planarizing the surface of a semiconductor substrate having irregularities.
[0346] As described above, the resist underlayer film forming composition of the present invention can realize a resist underlayer film having excellent embedding properties and flatness and exhibiting hardness that can withstand processing. Therefore, the resist underlayer film forming composition of the present invention is very useful even in the manufacturing method of a semiconductor device including pattern formation by a multilayer resist method as described above.
[0347] Example
[0348] Hereinafter, synthesis examples, comparative synthesis examples, embodiments, and comparative examples are shown to more specifically illustrate the present invention, but the present invention is not limited thereto. In addition, as for molecular weight, the weight average molecular weight (Mw) calculated as polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent is obtained.
[0349] [Synthesis example]
[0350] In the following synthesis examples and comparative synthesis examples, the aromatic compound Ar1 group shown below: any one of (Ar1-1) to (Ar1-8), the aldehyde compound group: any one of (G1) to (G3) ((G1) is a 36 to 38% aqueous solution), and the etherifying agent group: any one of (R1-1) to (R1-8) are used. The respective raw material groups are shown below.
[0351] [Chemistry 29]
[0352]
[0353] [Chemistry 30]
[0354]
[0355] [Chemistry 31]
[0356]
[0357] Ms is methanesulfonyl.
[0358] [Synthesis Example 1] Synthesis of Resist Underlayer Film-Forming Compound (A-1)
[0359] 5.0 g of an aromatic compound (Ar1-1), 6.9 g of an aldehyde compound (G2), 0.15 g of p-toluenesulfonic acid monohydrate, and 25 g of propylene glycol monomethyl ether (PGME) were mixed and stirred at 120°C for 20 hours. The mixture was returned to room temperature, 150 g of hexane was added thereto, and the upper layer was decanted. Thereafter, the residue was dissolved in 150 ml of methyl isobutyl ketone (MIBK) and washed twice with 100 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide (DMF) was added to the residue, and the solvent was removed under reduced pressure again. Thereafter, 11.0 g of potassium carbonate and 20 g of additional DMF were added to the residue, and stirred at 90°C. 11.7 g of an etherifying agent (R1-1) was added dropwise thereto, and after reacting for 5 hours, the temperature was lowered to 60°C. Then, 3.8 g of an etherifying agent (R1-2) was added to the mixture, and the mixture was reacted for 16 hours. The reactant was returned to room temperature, washed with 150 ml of MIBK and 150 ml of water, and then washed with 100 ml of a 3% nitric acid aqueous solution. After that, the reactant was washed with 150 ml of water 4 times, and the solvent was removed under reduced pressure. Then, 300 g of PGMEA was added to the residue, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a compound (A-1) for forming an anti-corrosion lower film of a novolac resin was obtained.
[0360] (A-1): Mw = 2198
[0361] [Chemistry 32]
[0362]
[0363] [Synthesis Example 2] Synthesis of Compound (A-2) for Forming Resist Underlayer Film
[0364] The aromatic compound (Ar1-1) 5.0 g used in Synthesis Example 1 was changed to an aromatic compound (Ar1-2) 5.0 g, the aldehyde compound (G2) was changed to 8.0 g, the amount of potassium carbonate added was changed to 12.6 g, the etherifying agent (R1-1) and (R1-2) were changed to etherifying agent (R1-3) 12.1 g and etherifying agent (R1-4) 5.4 g, respectively. Except for this, a PGMEA solution of the compound (A-2) for forming an anti-etching underlayer film as a phenolic varnish resin was obtained in the same manner as in Synthesis Example 1.
[0365] (A-2): Mw = 2439
[0366] [Chemistry 33]
[0367]
[0368] [Synthesis Example 3] Synthesis of Compound (A-3) for Forming Resist Underlayer Film
[0369] 5.0 g of an aromatic compound (Ar1-3), 5.5 g of an aldehyde compound (G3), 0.25 g of p-toluenesulfonic acid monohydrate, and 30 g of PGME are mixed and stirred at 120°C for 20 hours. The mixture is returned to room temperature and washed twice with 150 ml of MIBK and 100 ml of water. The solvent is removed under reduced pressure, 200 g of dimethylformamide is added to the residue, and the solvent is removed again under reduced pressure. Thereafter, 29.1 g of potassium carbonate and 60 g of additional DMF are added to the residue and stirred at 90°C. 14.0 g of an etherifying agent (R1-3) and 15.5 g of an etherifying agent (R1-7) are added dropwise thereto and reacted for 20 hours. The reactant is returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% aqueous nitric acid solution. Then, the reactant is washed 4 times with 200 ml of water, and the solvent is removed under reduced pressure. Then, 300 g of PGMEA was added to the residue, and the solvent was removed under reduced pressure to perform PGMEA substitution, thereby obtaining a PGMEA solution of a resist underlayer film-forming compound (A-3) which is a novolac resin.
[0370] (A-3): Mw = 2251
[0371] [Chemistry 34]
[0372]
[0373] [Synthesis Example 4] Synthesis of Compound (A-4) for Forming Resist Underlayer Film
[0374] The condensation reaction of the aromatic compound and the aldehyde compound and the solvent replacement are carried out in the same manner as in Synthesis Example 3. Thereafter, 27.4 g of potassium carbonate and additional 60 g of DMF are added to the reactant, and the mixture is stirred at 90°C. 14.0 g of the etherifying agent (R1-3) is added dropwise thereto, and after reacting for 5 hours, 21.0 g of the etherifying agent (R1-5) is added dropwise, and the mixture is reacted at 55°C for 20 hours. The reactant is returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reactant is washed 4 times with 200 ml of water, and the solvent is removed under reduced pressure. Then, 300 g of PGMEA is added to the residue, and the solvent is removed under reduced pressure to perform PGMEA replacement. In this way, a PGMEA solution of a compound (A-4) for forming an anti-etching lower film as a phenolic varnish resin is obtained.
[0375] (A-4): Mw = 2320
[0376] [Chemistry 35]
[0377]
[0378] [Synthesis Example 5] Synthesis of Compound (A-5) for Forming Resist Underlayer Film
[0379] 10.0 g of an aromatic compound (Ar1-4), 4.8 g of an aldehyde compound (G1), 0.3 g of p-toluenesulfonic acid monohydrate, and 45 g of PGME were mixed and stirred at 120°C for 20 hours. The mixture was returned to room temperature and washed twice with 150 ml of MIBK and 100 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added to the residue, and the solvent was removed again under reduced pressure. Thereafter, 17.3 g of potassium carbonate and 100 g of additional DMF were added to the residue and stirred at 90°C. 18.3 g of an etherifying agent (R1-3) was added dropwise thereto, and after reacting for 5 hours, 3.7 g of an etherifying agent (R1-4) was added and reacted at 55°C for 16 hours. The reactant was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% aqueous nitric acid solution. Then, the reaction product was washed four times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a resist underlayer film-forming compound (A-5) which is a novolac resin was obtained.
[0380] (A-5): Mw = 5594
[0381] [Chemistry 36]
[0382]
[0383] [Synthesis Example 6] Synthesis of Compound (A-6) for Forming Resist Underlayer Film
[0384] 10.0 g of an aromatic compound (Ar1-5), 7.8 g of an aldehyde compound (G3), 7.0 g of a 25% aqueous sodium hydroxide solution, and 50 g of PGME were mixed and stirred at 120°C for 20 hours. The mixture was returned to room temperature, 300 g of hexane was added thereto, and the upper layer was decanted. Then, 20 g of PGME was added to the residue, 200 g of hexane was added again, and the upper layer was decanted. The residue was dissolved in 150 ml of MIBK and washed twice with 100 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added to the residue, and the solvent was removed under reduced pressure again. Thereafter, 34.5 g of potassium carbonate and 50 g of additional DMF were added to the residue, and the mixture was stirred at 90°C. 33.2 g of an etherifying agent (R1-3) was added dropwise thereto, and after reacting for 5 hours, 12.4 g of an etherifying agent (R1-5) was added, and the mixture was reacted at 55°C for 16 hours. The reactant was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reactant was washed 4 times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a compound (A-6) for forming a resist underlayer film as a novolac resin was obtained.
[0385] (A-6): Mw = 5501
[0386] [Chemistry 37]
[0387]
[0388] [Synthesis Example 7] Synthesis of Compound (A-7) for Forming Resist Underlayer Film
[0389] The aldehyde compound (G3) 7.8g used in Synthesis Example 6 was changed to aldehyde compound (G2) 11.0g, the amount of potassium carbonate added was changed to 17.3g, and the etherifying agent was changed to etherifying agent (R1-3) 16.6g and etherifying agent (R1-4) 6.5g. Except for this, a PGMEA solution of the compound (A-7) for forming an anti-etching underlayer film as a phenolic varnish resin was obtained in the same manner as in Synthesis Example 6.
[0390] (A-7): Mw = 4425
[0391] [Chemistry 38]
[0392]
[0393] [Synthesis Example 8] Synthesis of Compound (A-8) for Forming Resist Underlayer Film
[0394] 5.0 g of an aromatic compound (Ar1-2), 5.0 g of an aromatic compound (Ar1-6), 4.5 g of an aldehyde compound (G1), 0.30 g of p-toluenesulfonic acid monohydrate, and 40 g of PGME were mixed and stirred at 120°C for 20 hours. The mixture was returned to room temperature, 200 g of water was added thereto, and the upper layer was decanted. Thereafter, the residue was dissolved in 200 ml of MIBK and washed twice with 150 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added to the residue, and the solvent was removed under reduced pressure again. Thereafter, 22.0 g of potassium carbonate and 50 g of additional DMF were added to the residue, and the mixture was stirred at 80°C. 20.7 g of an etherifying agent (R1-3) was added dropwise thereto, and after reacting for 5 hours, 9.5 g of an etherifying agent (R1-4) was added, and the mixture was reacted at 55°C for 16 hours. The reactant was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reactant was washed 4 times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a compound (A-8) for forming a resist underlayer film as a novolac resin was obtained.
[0395] (A-8): Mw = 3755
[0396] [Chemistry 39]
[0397]
[0398] [Synthesis Example 9] Synthesis of Compound (A-9) for Forming Resist Underlayer Film
[0399] 10.0 g of an aromatic compound (Ar1-7), 1.6 g of an aldehyde compound (G1), 0.3 g of p-toluenesulfonic acid monohydrate, and 30 g of PGME were mixed and stirred at 120°C for 20 hours. After the mixture was returned to room temperature, 120 g of water was added dropwise thereto, and the upper layer was decanted. The residue was washed twice with 200 ml of MIBK and 150 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added, and the solvent was removed again under reduced pressure. Thereafter, 16.2 g of potassium carbonate and 80 g of additional DMF were added to the residue, stirred at 90°C, 15.6 g of an etherifying agent (R1-3) and 2.9 g of an etherifying agent (R1-7) were added dropwise thereto, and the mixture was reacted for 20 hours. The reactant was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% aqueous nitric acid solution. Then, the reaction product was washed four times with 200 ml of water, and 300 g of PGMEA was added to the solvent under reduced pressure, and the solvent was removed under reduced pressure to replace PGMEA. Thus, a PGMEA solution of a resist underlayer film-forming compound (A-9) which is a novolac resin was obtained.
[0400] (A-9): Mw = 4515
[0401] [Chemistry 40]
[0402]
[0403] [Synthesis Example 10] Synthesis of Compound (A-10) for Forming Resist Underlayer Film
[0404] The condensation reaction of the aromatic compound and the aldehyde compound and the solvent replacement are carried out in the same manner as in Synthesis Example 9. Thereafter, 16.2 g of potassium carbonate and 80 g of additional DMF are added to the reactant, and the mixture is stirred at 90°C. 15.6 g of an etherifying agent (R1-3) is added dropwise thereto, and after reacting for 5 hours, 5.8 g of an etherifying agent (R1-5) is added, and the mixture is reacted at 55°C for 16 hours. The reactant is returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reactant is washed 4 times with 200 ml of water, and the solvent is removed under reduced pressure. Then, 300 g of PGMEA is added to the residue, and the solvent is removed under reduced pressure to perform PGMEA replacement. In this way, a PGMEA solution of a compound (A-10) for forming an anti-etching lower film as a phenolic varnish resin is obtained.
[0405] (A-10): Mw = 4678
[0406] [Chemistry 41]
[0407]
[0408] [Synthesis Example 11] Synthesis of Compound (A-11) for Forming Resist Underlayer Film
[0409] A PGMEA solution of a resist underlayer film-forming compound (A-11) which is a novolac resin was obtained in the same manner as in Synthesis Example 10 except that the etherifying agent (R1-3) used in Synthesis Example 10 was changed to 17.1 g of the etherifying agent (R1-7).
[0410] (A-11): Mw = 4705
[0411] [Chemistry 42]
[0412]
[0413] [Synthesis Example 12] Synthesis of Compound (A-12) for Forming Resist Underlayer Film
[0414] A PGMEA solution of a resist underlayer film-forming compound (A-12) which is a novolac resin was obtained in the same manner as in Synthesis Example 9, except that the etherifying agent (R1-3) used in Synthesis Example 10 was changed to 19.4 g of the etherifying agent (R1-8).
[0415] (A-12): Mw = 4611
[0416] [Chemistry 43]
[0417]
[0418] [Synthesis Example 13] Synthesis of Compound (A-13) for Forming Resist Underlayer Film
[0419] A PGMEA solution of a resist underlayer film-forming compound (A-13) which is a novolac resin was obtained in the same manner as in Synthesis Example 10 except that the added amount of the aldehyde compound (G1) used in Synthesis Example 10 was changed to 2.0 g.
[0420] (A-13): Mw = 7600
[0421] [Chemistry 44]
[0422]
[0423] [Synthesis Example 14] Synthesis of Compound (A-14) for Forming Resist Underlayer Film
[0424] 10.0 g of an aromatic compound (Ar1-8), 1.7 g of an aldehyde compound (G1), 0.25 g of p-toluenesulfonic acid monohydrate, and 30 g of PGME were mixed and stirred at 120°C for 20 hours. The mixture was returned to room temperature, 200 g of hexane was added thereto, and the upper layer was decanted. The residue was dissolved in 150 ml of MIBK and washed twice with 100 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added to the residue, and the solvent was removed under reduced pressure again. Thereafter, 8.1 g of potassium carbonate and 50 g of additional DMF were added to the residue, stirred at 90°C, 7.8 g of an etherifying agent (R1-3) was added dropwise thereto, and after reacting for 5 hours, 2.8 g of an etherifying agent (R1-6) was added, and the mixture was reacted at 55°C for 16 hours. The reaction product was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and then washed with 150 ml of a 3% nitric acid aqueous solution. The reaction product was then washed with 200 ml of water four times, the solvent was removed under reduced pressure, 300 g of PGMEA was added, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a novolac resin resist underlayer film forming compound (A-14) was obtained.
[0425] (A-14): Mw = 5850
[0426] [Chemistry 45]
[0427]
[0428] [Synthesis Example 15] Synthesis of Compound (A-15) for Forming Resist Underlayer Film
[0429] 5.0 g of an aromatic compound (Ar1-5), 2.7 g of an aldehyde compound (G3), 0.25 g of p-toluenesulfonic acid monohydrate, and 30 g of PGME were mixed, and the mixture was stirred at 120°C for 8 hours. Then, 1.6 g of an aldehyde compound (G1) was added to the mixture, and the mixture was reacted for another 12 hours. The reactant was dissolved in 150 ml of MIBK and washed twice with 100 ml of water. The solvent was removed under reduced pressure, 200 g of dimethylformamide was added to the residue, and the solvent was removed under reduced pressure again. Then, 21.9 g of potassium carbonate and 50 g of additional DMF were added to the residue, and the mixture was stirred at 90°C. 15.6 g of an etherifying agent (R1-3) was added dropwise thereto, and the mixture was reacted for 5 hours. Then, 11.2 g of an etherifying agent (R1-5) was added, and the mixture was reacted at 55°C for 16 hours. The reactant was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reactant was washed 4 times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of a compound (A-15) for forming a resist underlayer film as a novolac resin was obtained.
[0430] (A-15): Mw = 3670
[0431] [Chemistry 46]
[0432]
[0433] [Comparative Synthesis Example 1] Synthesis of Resist Underlayer Film-Forming Compound (R-1)
[0434] A PGMEA solution of a resist underlayer film-forming compound (R-1) which is a novolac resin was obtained in the same manner as in Synthesis Example 5 except that the etherifying agent in Synthesis Example 5 was changed to only 20.4 g of (R1-4) and the reaction temperature was fixed at 55°C.
[0435] (R-1): Mw = 5324
[0436] [Chemistry 47]
[0437]
[0438] [Comparative Synthesis Example 2] Synthesis of Resist Underlayer Film-Forming Compound (R-2)
[0439] 10.0 g of 1,5-dihydroxynaphthalene, 10.13 g of 4-tert-butylbenzaldehyde, 50 g of PGMEA, and 1.2 g of methanesulfonic acid were mixed and reacted at 150 ° C for 2 hours. After the reaction was terminated, the reaction solution was added dropwise to a mixed solution of methanol / water, reprecipitated, and the supernatant was decanted. 100 g of PGMEA was added to the residue, and the mixture was dried under reduced pressure to perform solvent replacement. In this way, a PGMEA solution of a compound (R-2) for forming an anti-corrosion lower film as a novolac resin was obtained.
[0440] (R-2): Mw = 4110
[0441] [Chemistry 48]
[0442]
[0443] [Comparative Synthesis Example 3] Synthesis of Resist Underlayer Film-Forming Compound (R-3)
[0444] Mix 10.0 g of phenylnaphthylamine, 8.2 g of 9-fluorenone, 1.3 g of methanesulfonic acid, and 20 g of propylene glycol monomethyl ether acetate. Then, heat to reflux under nitrogen and react for 14 hours. After the reaction stops, reprecipitate the reactant with methanol and decant the upper layer. Add 100 g of PGMEA to the residue and dry it under reduced pressure. In this way, a PGMEA solution of a compound (R-3) for forming an anti-corrosive lower film as a novolac resin is obtained.
[0445] (R-3): Mw = 1900
[0446] [Chemistry 49]
[0447]
[0448] [Resist underlayer film forming composition UDL-1]
[0449] The compound for forming a resist underlayer film (A-1) was dissolved in propylene glycol monomethyl ether acetate (PGMEA) containing 0.5% by mass of a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) at the ratio shown in Table 1, and the mixture was filtered through a 0.02 μm membrane filter to prepare a composition for forming a resist underlayer film (UDL-1).
[0450] [Preparation of Resist Underlayer Film-forming Compositions (UDL-2 to 26) and Resist Underlayer Film-forming Compositions for Comparative Examples (UDL-1 to 3 for Comparative Examples)]
[0451] The types and contents of the components were set as shown in Table 1. The same operation as in the resist underlayer film-forming composition (UDL-1) was performed to adjust the chemical solutions. In Table 1, "-" indicates that the component was not used. The crosslinking agent was represented by the following formula (D-1), the thermally decomposable resin was represented by the following formula (E-1), the high boiling point solvent was 1,6-diacetoxyhexane (B2-1): boiling point 260°C, and the thermal acid generator was represented by the following formula (TAG-1).
[0452] [Crosslinking agent]
[0453] The cross-linking agent (D-1) used in the resist underlayer film forming composition is shown below.
[0454] [Chemistry 50]
[0455]
[0456] [Synthesis Example of Pyrolyzable Resin] Synthesis of Pyrolyzable Resin (E-1)
[0457] 100 g of diethylene glycol monovinyl ether was added to a mixture of 3.8 g of cation exchange resin (Amberlyst (registered trademark) 15) and 100 g of ethyl acetate at room temperature, and the mixture was stirred for 3 hours. 0.8 g of triethylamine was added to the obtained mixture, and after the reaction was stopped, the cation exchange resin was removed by filtration. The filtrate was concentrated under reduced pressure to obtain 100 g of thermally decomposable resin (E-1) as a highly viscous liquid.
[0458] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the results were as follows: Mw = 5,200, Mw / Mn = 2.64.
[0459] [Chemistry 51]
[0460]
[0461] [Thermal acid generator]
[0462] The thermal acid generator (TAG-1) used in the resist underlayer film forming composition is shown below.
[0463] [Chemistry 52]
[0464]
[0465] [Table 1]
[0466]
[0467]
[0468] [Solvent resistance test]
[0469] The resist underlayer film-forming compositions (UDL-1 to 26, comparative examples UDL-1 to 3) prepared above were each applied on a silicon substrate to obtain a coating film. The obtained coating film was calcined at 180° C. for 60 seconds and then calcined at 350° C. for 60 seconds. Thus, each resist underlayer film having a film thickness of about 200 nm was formed.
[0470] The film thickness (FT-1 [nm]) of the formed resist underlayer film was measured. Then, OK73 diluent (propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate = 7 / 3) was placed on the resist underlayer film, and then allowed to stand for 30 seconds. The resist underlayer film was then spin-dried, and then the resist underlayer film was baked at 100°C for 60 seconds to evaporate the OK73 diluent (rework). The film thickness (FT-2 [nm]) of the resist underlayer film after rework was measured in this manner.
[0471] The difference in film thickness before and after the treatment was determined (residual film ratio: (FT-2 / FT-1)×100). The results are shown in Table 2 below.
[0472] [Contact angle measurement and hardness measurement]
[0473] The resist underlayer film-forming compositions (UDL-1 to 26, comparative examples UDL-1 to 3) prepared above were each applied on a silicon substrate to obtain a coating film. The coating film was then calcined at 180° C. for 60 seconds and then calcined at 350° C. for 60 seconds. Thus, each resist underlayer film having a film thickness of about 200 nm was formed.
[0474] The contact angle of the resist underlayer films with pure water was measured. The hardness of the resist underlayer films was measured by nanoindentation test using a nanoindenter SA2 manufactured by TOYO Corporation. The results are shown in Table 2.
[0475] [Table 2]
[0476]
[0477]
[0478] As shown in Table 2, the residual film rates ((FT-2 / FT-1)×100) before and after reprocessing of Examples 1-1 to 1-15 of the resist underlayer film forming composition of the present invention all exceeded 100.5%, indicating that the film after calcination became a porous film having a large number of pores such that the OK73 diluent can penetrate, and the film density was low. In addition, the residual film rates of Examples 1-9 to 1-14 having a spirocyclic structure in the mother core were 102%<((FT-2 / FT-1)×100) and exceeded 102%, indicating that the porosity was further improved by the effects of the cyclic alkyl structure of the mother core and the cyclic alkyl ether of the substituent. Furthermore, Examples 1-16 to 1-19 to which a crosslinking agent was added showed that the residual film rate before and after reworking ((FT-2 / FT-1)×100) was slightly suppressed compared to the corresponding examples of Examples 1-4, 1-5, 1-7 and 1-10 to which no crosslinking agent was added, and on the other hand, the hardness was increased, resulting in improved processing resistance. Furthermore, Examples 1-20 to 1-23 to which a pyrolyzable resin was added showed that the residual film rate before and after reworking ((FT-2 / FT-1)×100) was increased compared to the corresponding examples of Examples 1-4, 1-5, 1-7 and 1-10 to which no crosslinking agent was added. It can be understood from this that the porosity can be adjusted by adding a crosslinking agent and a pyrolyzable resin.
[0479] In Comparative Example 1-1 in which R1 was a single compound in the same resin and Comparative Example 1-2 in which R1 was not ether-substituted, the improvement in the residual film ratio was low and the porosity was insufficient.
[0480] In Comparative Example 1-3, it is understood that no improvement in the residual film ratio was observed and the porosity was poor.
[0481] In addition, regarding the contact angle, Examples 1-1, 1-2, and 1-7 in which fluorine was introduced had a high contact angle of 60° or more, and those in which fluorine was introduced had a contact angle of about 50°, and it was also confirmed that it was possible to flexibly use the gas according to the hydrophilicity and hydrophobicity of the gas type used. In addition, the hardness measured as an indicator of processing resistance also exceeded 0.6 GPa in most cases, and some were 0.8 GPa, and it was also confirmed that the hardness had sufficient processing resistance.
[0482] [Landfill characteristics evaluation]
[0483] The resist underlayer film-forming compositions prepared above (UDL-1 to 26, comparative examples UDL-2 to 3) were coated on SiO2 wafer substrates having a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, and distance between the centers of two adjacent holes 0.32 μm), and the coated films were calcined at 180°C for 60 seconds and then calcined at 350°C for 60 seconds. Thus, each resist underlayer film with a film thickness of 200 nm was formed on the substrate having a dense hole pattern.
[0484] The cross-sectional shape of each wafer substrate obtained was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. to confirm whether there are no pores (voids) inside the holes and whether they are filled with organic films. The results are shown in Table 3 below. When a composition for forming a resist underlayer film with poor filling characteristics is used, pores will be generated inside the holes. When a composition for forming a resist underlayer film with good filling characteristics is used, in this evaluation, the organic film is filled inside the holes without pores. The evaluation is as follows. A: No pores and can be filled, B: There are tiny pores, C: There are pores or it cannot be filled.
[0485] [Table 3]
[0486]
[0487]
[0488] As shown in Table 3, in Examples 2-1 to 2-26 using the resist underlayer film forming composition (UDL-1 to 26) of the present invention, it was confirmed that, except for Example 2-13, no voids were generated, dense hole patterns could be filled, and good filling characteristics were obtained. The polymer used in Example 2-13, in which voids were found at the bottom, had a larger molecular weight than the others, and it is presumed that it could not be filled at the bottom without gaps, and appeared as voids after calcination.
[0489] Comparative Example 2-1 using Comparative Example UDL-2 failed to fill the pattern. This is probably because the compound R-2 in Comparative Example UDL-2 has no ether substituent and originally has a rigid resin structure, so the resin has low fluidity and cannot fill the fine pattern.
[0490] In addition, in Comparative Example 2-2 using Comparative Example UDL-3, larger pores were observed at the bottom than in Example 2-13. This is considered to be because the resin of Comparative Example UDL-3 has no crosslinking properties in itself, but a large amount of crosslinking agent, thermal acid generator, etc. are added, so there are many decomposition and sublimation products of the resin and additives.
[0491] [Planarization characteristics evaluation]
[0492] The resist lower film forming composition prepared above is coated on a SiO2 wafer substrate having a huge isolated groove pattern (groove width 10μm, groove depth 0.1μm), and the obtained coating film is calcined at 180°C for 60 seconds, and then calcined at 350°C for 60 seconds. In this way, each resist lower film is formed on a substrate having a huge isolated groove pattern. The height difference of the resist lower film between the groove part and the non-groove part is observed using the NX10 atomic force microscope (AFM) manufactured by Park Systems. The results are shown in Table 4. In this evaluation, the smaller the height difference, the better the flattening characteristics. In addition, in this evaluation, the groove pattern with a depth of 0.10μm is flattened using an organic film forming composition with a usual film thickness of about 0.2μm to evaluate the pros and cons of the flattening characteristics, so it is a strict evaluation condition.
[0493] [Table 4]
[0494]
[0495] As shown in Table 4, Examples 3-1 to 3-4 using the resist underlayer film forming compositions UDL-4, 5, 7 and 10 of the present invention were confirmed to have a small height difference between the pattern portion and the non-pattern portion of the film and excellent planarization characteristics compared to Comparative Example 3-2 having no ether structure and Comparative Example 3-3 having a very different resin structure. In addition, Examples 3-1 to 3-4 were confirmed to have a small height difference and excellent planarization characteristics compared to Comparative Example 3-1 in which R1 of the general formula (1) was set to a single structure and all were set to the same ether structure in the same resin. It is understood that by including a plurality of ether structures as in the general formula (1), thermal fluidity is improved and excellent planarization characteristics are exhibited. In particular, Example 3-4 using the resist underlayer film forming composition UDL-10 synthesized with a resist underlayer film forming compound (A-10) containing other carboxylic acids with mixed alkyl chain lengths exhibited more excellent planarization characteristics.
[0496] In addition, compared with Examples 3-1 to 3-4 to which a crosslinking agent (D-1) and a pyrolyzable resin (E-1) were added, there was no significant change in flatness. It is believed that the addition of a crosslinking agent and a pyrolyzable resin that can adjust the porosity of the membrane did not significantly affect the flatness. In addition, in Example 3-14 to which a high boiling point solvent (B2-1) was added, the flatness was improved compared with Example 3-1 to which a high boiling point solvent (B2-1) was not added. It is believed that this is because the thermal fluidity is improved by the high boiling point solvent.
[0497] As described above, the resist underlayer film forming composition of the present invention can form a film that can be used as an underlayer film, exhibits high degree of embedding and planarization characteristics, has high hardness and excellent processing resistance, and is porous and low-density, so it can provide a resist underlayer film with excellent air permeability. Such a resist underlayer film is particularly useful in nanoimprinting and is also suitable for use in a multilayer resist process.
[0498] This manual contains the following aspects.
[0499] [1] A composition for forming a resist underlayer film, comprising: (A) a novolac resin having a repeating unit structure represented by the following general formula (I) and / or (II), and (B) an organic solvent;
[0500] [Chemistry 53]
[0501]
[0502] In the general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted aryl groups having 6 to 30 carbon atoms bonded to each other via linear, branched or cyclic hydrocarbon groups, ether groups or carbonyl groups. Ar1 may be one or a combination of multiple groups in the same resin, and Ar2 may be one or a combination of multiple groups in the same resin. R1 in the same resin is A combination of at least two or more of them is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; n1 is an integer greater than 1, and n2, n3 and n4 are integers greater than 0.
[0503] [2] The resist underlayer film forming composition according to [1], wherein in the formula (I) and (II), at least one of R1 is a structure R selected from the group consisting of the groups represented by the following formula (III-1): 1-1 ;
[0504] [Chemistry 54]
[0505]
[0506] In formula (III-1), * represents a bonding site with an oxygen atom.
[0507] [3] The resist underlayer film forming composition according to [1], wherein in the formula (I) and (II), R1 is a structure R selected from the group consisting of the groups represented by the following formula (III-1): 1-1 and a structure R selected from the group consisting of groups represented by the following formula (III-2): 1-2 Combination of structure R 1-1 The ratio is set to a, and the structure R 1-2 When the ratio is set to b, the ratios a and b satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100;
[0508] [Chemistry 55]
[0509]
[0510] In formulae (III-1) and (III-2), * represents a bonding site to an oxygen atom.
[0511] [4] The composition for forming a resist underlayer film according to any one of [1] to [3], wherein in the general formula (II), Ar2 is a benzene ring.
[0512] [5] The resist underlayer film forming composition according to any one of [1] to [4], wherein in the general formula (I) and (II), Ar1 is selected from the group consisting of the structure represented by the following formula (Ar-1);
[0513] [Chemistry 56]
[0514]
[0515] [6] The composition for forming a resist underlayer film according to any one of [1] to [5], wherein in the general formula (II), n3+n4 is an integer greater than 2.
[0516] [7] The resist underlayer film forming composition according to any one of [1] to [6], wherein the novolac resin (A) has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 8,000 as determined by gel permeation chromatography.
[0517] [8] A composition for forming a resist underlayer film as described in any one of [1] to [7], wherein the thickness of a coating film obtained by applying the composition for forming a resist underlayer film to a substrate, calcining the coating film at 180°C for 60 seconds, and then calcining the coating film at 350°C for 60 seconds is defined as FT-1, and after the calcination, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is placed on the coating film, followed by allowing the mixture to stand for 30 seconds, spin drying the coating film, and then baking the coating film at 100°C for 60 seconds to evaporate the OK73 diluent is defined as FT-2, which is 100.5<{(FT-2) / (FT-1)}×100.
[0518] [9] The resist underlayer film forming composition according to any one of [1] to [8], further comprising (C) a surfactant.
[0519]
[10] The resist underlayer film forming composition of any one of [1] to [7] further comprises (D) a cross-linking agent, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to calcination at 180°C for 60 seconds, and then subjected to additional calcination at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional calcination, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is arranged on the coating film, and then allowed to stand for 30 seconds, and then the coating film is subjected to spin drying, and then the coating film is subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2, which satisfies 100<{(FT-2) / (FT-1)}×100<101.
[0520]
[11] The resist underlayer film forming composition of any one of items [1] to [7] further comprises (E) a thermally decomposable resin, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to calcination at 180°C for 60 seconds, and then subjected to additional calcination at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional calcination, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is arranged on the coating film, and then allowed to stand for 30 seconds, and then the coating film is subjected to spin drying, and then the coating film is subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2, which becomes 101<{(FT-2) / (FT-1)}×100.
[0521]
[12] The resist underlayer film forming composition of any one of [1] to [7] further comprises both (D) a crosslinking agent and (E) a thermally decomposable resin, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to calcination at 180°C for 60 seconds, and then subjected to additional calcination at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional calcination, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is arranged on the coating film, and then allowed to stand for 30 seconds, and then the coating film is subjected to spin drying, and then the coating film is subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2, which becomes 100<{(FT-2) / (FT-1)}×100.
[0522]
[13] The resist underlayer film forming composition according to any one of [1] to
[12] , further comprising (F) an acid generator.
[0523]
[14] The resist underlayer film forming composition according to any one of [1] to
[13] , wherein the resist underlayer film forming composition is for nanoimprinting.
[0524]
[15] A resist underlayer film, characterized in that it is a cured product of a coating film composed of a resist underlayer film forming composition as described in any one of [1] to
[13] .
[0525]
[16] A method for manufacturing a resist underlayer film, comprising the following steps:
[0526] The resist underlayer film forming composition according to any one of [1] to
[13] is applied onto a semiconductor substrate to obtain a coating film,
[0527] The coated film is fired to obtain a resist underlayer film.
[0528]
[17] A pattern forming method, characterized by comprising the following steps:
[0529] A resist underlayer film is formed on a semiconductor substrate using the resist underlayer film forming composition according to any one of [1] to
[13] ,
[0530] forming a hardening composition film on the resist underlayer film,
[0531] The curable composition film is brought into contact with a mold,
[0532] The curable composition film is irradiated with light or electron beam to form a cured film.
[0533] The cured film is separated from the mold.
[0534]
[18] The pattern forming method of
[17] , wherein the step of forming a hardening composition film on the resist underlayer film comprises:
[0535] An adhesion layer and / or a polysilicon oxide layer containing 99 mass % or less of Si is formed on the resist underlayer film by coating or vapor deposition, and a curable composition film is formed thereon.
[0536]
[19] A method for manufacturing a semiconductor device, comprising the following steps:
[0537] A resist underlayer film is formed on a semiconductor substrate using the resist underlayer film forming composition according to any one of [1] to
[13] ,
[0538] forming a resist film on the resist underlayer film,
[0539] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0540] Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film,
[0541] The semiconductor substrate is processed using the patterned underlayer film as a mask.
[0542]
[20] A method for manufacturing a semiconductor device, comprising the following steps:
[0543] A resist underlayer film is formed on a semiconductor substrate using the resist underlayer film forming composition according to any one of [1] to
[13] ,
[0544] forming a hard mask on the resist underlayer film,
[0545] Then, a resist film is formed on the hard mask film.
[0546] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.
[0547] The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask,
[0548] Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film,
[0549] The semiconductor substrate is processed using the patterned resist underlayer film as a mask.
[0550] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely illustrative, and any device having the technical concept and substantially the same configuration as described in the claims of the present invention and having the same functions and effects is included in the technical scope of the present invention.
Claims
1. A composition for forming a resist underlayer film, characterized in that: Include: (A) a novolac resin having a repeating unit structure represented by the following general formula (I) and / or (II), and (B) an organic solvent; In the general formulae (I) and (II), Ar1 and Ar2 are independently substituted or unsubstituted aryl groups having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl groups having 6 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or an ether ring, or substituted or unsubstituted aryl groups having 6 to 30 carbon atoms bonded to each other via linear, branched or cyclic hydrocarbon groups, ether groups or carbonyl groups. Ar1 may be one or a combination of multiple groups in the same resin, and Ar2 may be one or a combination of multiple groups in the same resin. R1 in the same resin is A combination of at least two or more of them is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; n1 is an integer greater than 1, and n2, n3 and n4 are integers greater than 0.
2. The resist underlayer film forming composition according to claim 1, wherein In the formulae (I) and (II), at least one of R1 is a structure R selected from the group consisting of groups represented by the following formula (III-1): 1-1 ; In formula (III-1), * represents a bonding site with an oxygen atom.
3. The resist underlayer film forming composition according to claim 1, wherein In the formulae (I) and (II), R1 is a structure R selected from the group consisting of the groups shown in the following formula (III-1): 1-1 and a structure R selected from the group consisting of groups represented by the following formula (III-2): 1-2 Combination of structure R 1-1 The ratio is set to a, and the structure R 1-2 When the ratio is set to b, the ratios a and b satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100; In formulae (III-1) and (III-2), * represents a bonding site to an oxygen atom.
4. The resist underlayer film forming composition according to claim 1, wherein In the general formula (II), Ar2 is a benzene ring.
5. The resist underlayer film forming composition according to claim 1, wherein In the general formula (I) and (II), Ar1 is selected from the group consisting of the structures shown in the following formula (Ar-1); 6. The resist underlayer film forming composition according to claim 1, wherein In the general formula (II), n3+n4 is an integer of 2 or more.
7. The resist underlayer film forming composition according to claim 1, wherein The (A) novolac resin has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 8,000 as determined by gel permeation chromatography.
8. The resist underlayer film forming composition according to claim 1, wherein The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 100.5<{(FT-2) / (FT-1)}×100. 9 . The resist underlayer film forming composition according to claim 1 , further comprising (C) a surfactant.
10. The resist underlayer film forming composition according to claim 1, further comprising (D) a crosslinking agent, The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 100<{(FT-2) / (FT-1)}×100<101.
11. The resist underlayer film forming composition according to claim 1, further comprising (E) a thermally decomposable resin, The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 101<{(FT-2) / (FT-1)}×100.
12. The resist underlayer film forming composition according to claim 1, further comprising both (D) a crosslinking agent and (E) a thermally decomposable resin. The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to calcination at 180° C. for 60 seconds, and then subjected to additional calcination at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional calcination, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 100<{(FT-2) / (FT-1)}×100. 13 . The resist underlayer film forming composition according to claim 1 , further comprising (F) an acid generator.
14. The resist underlayer film forming composition according to any one of claims 1 to 13, wherein The resist underlayer film forming composition is for nanoimprinting.
15. A resist underlayer film, characterized in that: A cured product of a coating film composed of the resist underlayer film forming composition according to any one of claims 1 to 13.
16. A method for manufacturing a resist underlayer film, characterized in that: The following steps are involved: The resist underlayer film forming composition according to any one of claims 1 to 13 is applied onto a semiconductor substrate to obtain a coating film, The coated film is fired to obtain a resist underlayer film.
17. A pattern forming method, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 13, forming a hardening composition film on the resist underlayer film, The curable composition film is brought into contact with a mold, The curable composition film is irradiated with light or electron beam to form a cured film. The cured film is separated from the mold.
18. The pattern forming method according to claim 17, wherein: The step of forming a hardening composition film on the resist underlayer film comprises: An adhesion layer and / or a polysilicon oxide layer containing 99 mass % or less of Si is formed on the resist underlayer film by coating or vapor deposition, and a curable composition film is formed thereon.
19. A method for manufacturing a semiconductor device, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 13, forming a resist film on the resist underlayer film, The resist film is irradiated with light or electron beams and then developed to form a resist pattern. Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film, The semiconductor substrate is processed using the patterned underlying film as a mask.
20. A method for manufacturing a semiconductor device, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 13, forming a hard mask on the resist underlayer film, Then, a resist film is formed on the hard mask film. The resist film is irradiated with light or electron beams and then developed to form a resist pattern. The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask, Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film, The semiconductor substrate is processed using the patterned resist underlayer film as a mask.
Citation Information
Patent Citations
Copying machine (metal cutting)
IE10958L
Image transferring drum
JP1983027180A
Method for forming graded structures using imprint lithography
JP2006524919A
Photoresist underlayer film forming material and pattern forming method
JP2007199653A
New photoacid generator, resist material using the same, and pattern forming method
JP2009269953A